Curable silicone composition, cured product thereof, and method for producing same
Patent Information
- Application Number
- JP2020562489
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-27
- Filing Date
- 2019-12-27
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2039-12-27
AI Technical Summary
【0022】 本発明の硬化性粒状シリコーン組成物は、ホットメルト性を有し、取扱い作業性および硬化特性に優れると共に、溶融時のギャップフィル性に優れ、小粒径の機能性無機フィラーを大量に含有しても、応力緩和に優れた柔軟な硬化物を形成することができる。さらに、本発明の硬化性粒状シリコーン組成物は、当該機能性無機フィラーの種類を変更することにより、硬化物に低線膨張率化、熱伝導率の付与、光反射性などを付与することができる。また、このような硬化性シリコーン組成物は、簡便な混合工程のみで生産することができ、効率よく製造することができる。また、本発明の硬化物は、半導体装置の部材として有用であり、本発明の成型方法を用いることで、これらの硬化物を用途に合わせて効率よく製造できる。
Smart Images

Figure 0007644604000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable granular silicone composition that can be obtained by a simple production method and has excellent hot melt properties and suppression of warping of the cured product against lead frames, etc. The present invention further relates to a cured product using the curable granular silicone composition, or pellets or sheets, a molding method for this cured product, and a semiconductor device comprising this cured product. [Background technology]
[0002] Curable silicone compositions are used in a wide range of industrial fields because they cure to form cured products that have excellent heat resistance, cold resistance, electrical insulation, weather resistance, water repellency, and transparency. Cured products of such curable silicone compositions generally do not discolor as easily as other organic materials, and the deterioration of physical properties is small, so they are also suitable as optical materials and sealants for semiconductor devices.
[0003] The present applicant has proposed a hot-melt curable granular silicone composition and a reactive silicone composition for molding in Patent Documents 1 and 2. These silicone compositions are made of so-called phenyl silicone resins, and have the advantages of superior hot-melt properties compared to methyl silicone resins, as well as superior hardness and strength of the cured product.
[0004] The present applicant has also proposed liquid (paste) curable silicone compositions in Patent Documents 3 and 4. However, these liquid or paste curable silicone compositions are insufficient in terms of handling, curing characteristics, and gap filling properties, and the flexibility and toughness of the cured product at temperatures from room temperature to high temperatures of about 150° C. are insufficient. In particular, the lack of flexibility of the cured product can cause problems such as warping and breakage.
[0005] On the other hand, Patent Documents 5 and 6 disclose hot-melt curable compositions using a mixed filler containing coarse particles. However, the storage modulus of the cured product at room temperature is extremely high (for example, 5000 MPa or more in Patent Document 5) and the cured product has poor flexibility, making it difficult to apply the composition to applications in which the composition is subject to deformation or bending at room temperature.
[0006] To solve these problems, the applicant has proposed a curable granular silicone composition containing an inorganic filler that is substantially free of coarse particles with an average particle size of 10.0 μm or more in Patent Document 7. This composition improves the flexibility and toughness of the cured product at temperatures from room temperature to high temperatures of about 150° C., and can suppress warping and breakage of the cured product to some extent.
[0007] However, in recent years, with the development of the semiconductor device industry, there is a strong demand for larger molding area and thinner molding thickness.Even with the above-mentioned curable granular silicone composition, under the conditions of molding method involving large-area thin film molding, especially integral molding with a thin substrate that is prone to warping, the cured product may warp or break, and there is a demand for a curable silicone composition that has hot melt properties, does not impair handling workability and curing properties, and further has excellent gap filling properties when melted, and has further improved flexibility and toughness at high temperatures from room temperature to about 150 ° C. Furthermore, in the existing curable silicone composition, when a relatively large amount of functional filler is blended, the stress relaxation property of the above-mentioned cured product decreases, and warping or breakage is likely to occur, especially during thin molding, and there is a problem that the trade-off problem between the content of functional filler and the stress relaxation property of the cured product cannot be solved. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2016 / 136243 Brochure [Patent Document 2] JP 2014-009322 A [Patent Document 3] International Publication No. 2016 / 038836 Brochure [Patent Document 4] JP 2013-076050 A [Patent Document 5] JP 2013-221075 A [Patent Document 6] International Publication No. 2013 / 051600 Brochure [Patent Document 7] International Publication No. 2018 / 030287 Brochure Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to provide a curable granular silicone composition that has hot melt properties, excellent handling and curing properties, and excellent gap-filling properties when melted, and can form a soft cured product that has excellent stress relaxation even if it contains a large amount of functional inorganic filler with a small particle size.The object of the present invention is to provide a method for efficiently producing such a curable silicone composition.Furthermore, the present invention is to provide a semiconductor device member made of such a curable silicone composition, a cured product such as a pellet or a sheet, a semiconductor device having the cured product, and a molding method for the cured product. [Means for solving the problem]
[0010] As a result of extensive investigations, the present inventors have discovered that: (A) organopolysiloxane resin fine particles having a curing reactive functional group; (B) a functional inorganic filler, and (C) containing a curing agent, By hardening, The storage modulus (G') at 25°C is 2000 MPa or less, The storage modulus (G') at 150°C is 100 MPa or less, The present inventors have found that the above problems can be solved by a curable granular silicone composition that gives a cured product having a peak value of loss tangent (tan δ), expressed as storage modulus / loss modulus (G' / G'') at a frequency of 1.0 Hz, of 0.40 or more, and have arrived at this invention. The above curable silicone composition may be in the form of pellets or sheets.
[0011] The above component (B) is preferably a functional inorganic filler which is one or more types of functional inorganic filler selected from a reinforcing filler, a white pigment, a thermally conductive filler, an electrically conductive filler, and an organic filler.
[0012] At least a part or the whole of the above component (A) is (A1) may be fine particles of a hot-melt organopolysiloxane resin having a softening point of 30° C. or higher and having a curing reactive functional group containing at least one carbon-carbon double bond in the molecule.
[0013] In addition, at least a part or the whole of the above component (A) is (A2-1) A compound that does not have hot melt properties as a whole molecule, has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and is SiO 4 / 2 and an organopolysiloxane resin fine particle containing siloxane units represented by the formula: (A2-2) A linear or branched organopolysiloxane that is liquid at 25°C and has a curing reactive functional group containing at least two carbon-carbon double bonds in the molecule. In addition to the above component (A2-1), (A2-1-2) may be a mixture of a compound having no hot melt properties as a whole molecule, a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and SiO 4 / 2 The organopolysiloxane resin may contain fine particles of an organopolysiloxane resin containing siloxane units represented by the following formula (1) in an amount of at least 20 mol % based on the total siloxane units.
[0014] In addition, the (B) component is preferably a filler that does not have a softening point or does not soften at or below the softening point of the (A) component, and is preferably substantially free of coarse particles with an average particle size of 5.0 μm or more. In addition, from the viewpoint of the functionality and physical properties of the cured product, the (B) component is preferably a reinforcing filler, a white pigment, a thermally conductive filler, an electrically conductive filler, a phosphor, or a mixture of at least two of these, and in particular, from the viewpoint of flexibility at room temperature to high temperatures and high gap-filling properties, it is particularly preferable that the (B) component contains (b1) an inorganic filler with an average particle size of 0.1 μm or less and (b2) an inorganic filler with an average particle size of 0.1 to 5.0 μm in a mass ratio of 1 / 99 to 50 / 50.
[0015] The content of the component (B) is preferably in the range of 10 to 50% by volume based on the total volume of the composition.
[0016] Such a curable granular silicone composition of the present invention is preferably in the form of pellets or sheets.
[0017] In particular, when the curable granular silicone composition of the present invention is in the form of a sheet, a laminate can be formed having a structure including a sheet-like member made of the curable granular silicone composition between two film-like substrates having a release layer. The sheet-like member has a thickness of 1 mm or less, is preferably a film-like adhesive, and can be handled as a peelable laminate.
[0018] The curable granular silicone composition of the present invention can be used in the form of a cured product, and can be used as a component for semiconductor equipment.
[0019] The curable granular silicone composition of the present invention and its cured product can be used in semiconductor devices, and the cured product can be used to form an encapsulant, light reflector, etc., to provide power semiconductor devices, optical semiconductor devices, and semiconductor devices mounted on flexible circuit boards. In particular, the curable granular silicone composition of the present invention has excellent gap-filling properties when molten, and its cured product has excellent flexibility and toughness at room temperature to high temperatures, so that it is suitable for providing semiconductor devices in which semiconductor elements are encapsulated together by so-called mold underfill or wafer molding, and encapsulated semiconductor element boards in which semiconductor elements are encapsulated with this cured product on a flexible circuit board that is intended to be used with deformation (bending, etc.).
[0020] The method for molding the curable granular silicone composition of the present invention comprises at least the following steps. (I) heating the pellet- or sheet-like curable granular silicone composition to at least 100°C to melt it; (II) a step of injecting the curable silicone composition obtained in step (I) into a mold, or a step of spreading the curable silicone composition obtained in step (I) throughout the mold by clamping the mold; and (III) A step of curing the curable silicone composition injected in the step (II) The above molding methods include transfer molding, compression molding, or injection molding, and the curable granular silicone composition of the present invention is preferably used as a molding material for these.Furthermore, the curable granular silicone composition of the present invention can be preferably used as a molding material for the so-called mold underfill method, which is a coating process in which the overmolding and underfilling of semiconductor elements are performed at once with the cured product, or the wafer molding method, which is an overmolding molding that covers the surface of a semiconductor wafer substrate carrying semiconductor elements and fills the gaps between the semiconductor elements, and can collectively seal relatively large wafers such as 8 inches or 12 inches.
[0021] In particular, the curable granular silicone composition of the present invention, particularly a pellet- or sheet-shaped curable granular silicone composition, can be used for sealing a large area of a semiconductor substrate (including a wafer). Furthermore, a sheet obtained by molding the curable granular silicone composition of the present invention into a sheet shape can be used for die attach films, sealing of flexible devices, stress relief layers for bonding two different substrates, etc. Effect of the Invention
[0022] The curable granular silicone composition of the present invention has hot melt properties, excellent handling workability and curing characteristics, and excellent gap filling properties when melted. Even if it contains a large amount of functional inorganic filler with a small particle size, it can form a flexible cured product with excellent stress relaxation. Furthermore, the curable granular silicone composition of the present invention can be given a low linear expansion coefficient, thermal conductivity, light reflectivity, etc. to the cured product by changing the type of the functional inorganic filler. In addition, such a curable silicone composition can be produced by only a simple mixing process and can be efficiently manufactured. In addition, the cured product of the present invention is useful as a component of a semiconductor device, and by using the molding method of the present invention, these cured products can be efficiently manufactured according to the application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] [Curable granular silicone composition] The curable granular silicone composition of the present invention comprises: (A) organopolysiloxane resin fine particles having a curing reactive functional group, (B) a functional inorganic filler, and (C) containing a curing agent, By hardening, The storage modulus (G') at 25°C is 2000 MPa or less, The storage modulus (G') at 150°C is 100 MPa or less, It is characterized by giving a cured product with a peak value of tan δ, expressed as storage modulus / loss modulus (G' / G'') at a frequency of 1.0 Hz, of 0.40 or more. In the present invention, unless otherwise specified, "having hot-melt properties" means having a softening point of 50°C or more, a melt viscosity at 150°C (preferably a melt viscosity of less than 1000 Pa s), and the property of flowing. On the other hand, when the softening point is 200°C or more, this is above the general usage temperature for molding applications, and is therefore defined as "not having hot-melt properties".
[0024] Each component of the composition and optional components will be described below. In the present invention, unless otherwise defined, "average particle size" refers to the primary average particle size of the particles. In addition, functional inorganic fillers with an average particle size of 10.0 μm or more may be referred to as "coarse particles."
[0025] Component (A) is the main component of the composition, and is organopolysiloxane resin fine particles having a curing reactive functional group that is cured by a curing agent (C). Here, the curing reactive functional group is one or more functional groups selected from a condensation reactive group, a hydrosilylation reactive group, a radical reactive group, and a peroxide curing group, with hydrosilylation reactive groups and radical reactive groups being preferred, and curing reactive functional groups containing a carbon-carbon double bond being particularly preferred.
[0026] Examples of the hydrosilylation reactive group in component (A) include alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl, and dodecenyl, and silicon-bonded hydrogen atoms. The hydrosilylation reactive group is preferably an alkenyl group. The alkenyl group may be linear or branched, and is preferably a vinyl group or a hexenyl group. It is preferable that component (A) has at least two hydrosilylation reactive groups in one molecule.
[0027] Examples of groups bonded to silicon atoms other than the hydrosilylation reactive groups in component (A) include alkyl groups having 1 to 20 carbon atoms, halogen-substituted alkyl groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, halogen-substituted aryl groups having 6 to 20 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, alkoxy groups, and hydroxyl groups. Specific examples include alkyl groups such as methyl groups, ethyl groups, propyl groups, butyl groups, pentyl groups, hexyl groups, heptyl groups, octyl groups, nonyl groups, decyl groups, undecyl groups, and dodecyl groups; aryl groups such as phenyl groups, tolyl groups, xylyl groups, naphthyl groups, anthracenyl groups, phenanthryl groups, and pyrenyl groups; aralkyl groups such as phenethyl groups and phenylpropyl groups; and groups in which some or all of the hydrogen atoms bonded to these groups have been substituted with halogen atoms such as chlorine atoms and bromine atoms; and alkoxy groups such as methoxy groups, ethoxy groups, and propoxy groups. Phenyl groups and hydroxyl groups are particularly preferred.
[0028] Examples of the radical reactive group in the (A) component include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl, and dodecenyl; acrylic-containing groups, such as 3-acryloxypropyl and 4-acryloxybutyl; methacrylic-containing groups, such as 3-methacryloxypropyl and 4-methacryloxybutyl; and silicon-bonded hydrogen atoms. The radical reactive group is preferably an alkenyl group. The alkenyl group may be linear or branched, and is preferably a vinyl group or a hexenyl group. The component (A) preferably has at least two radical reactive groups in one molecule.
[0029] Examples of groups bonded to silicon atoms other than the radical reactive groups in component (A) include halogen-substituted alkyl groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, halogen-substituted aryl groups having 6 to 20 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, alkoxy groups, and hydroxyl groups, and are the same as those mentioned above. In particular, phenyl groups and hydroxyl groups are preferred. In particular, component (A) preferably comprises 10 mol % or more of all organic groups in the molecule of aryl groups, particularly phenyl groups.
[0030] In the present invention, the (A) component contains organopolysiloxane resin fine particles having a curing reactive functional group, and the organopolysiloxane resin fine particles may have hot melt properties as a whole molecule, or may contain organopolysiloxane resin fine particles that do not have hot melt properties as a whole molecule. If the organopolysiloxane resin fine particles do not have hot melt properties, it is preferable that they are a mixture with a linear or branched organopolysiloxane. Furthermore, it is possible and preferable to use in combination organopolysiloxane resin fine particles that do not have a curing reactive functional group and do not have hot melt properties as a whole molecule.
[0031] That is, at least a part or all of the (A) component is (A1) Fine particles of a hot-melt organopolysiloxane resin having a softening point of 30° C. or higher and a curing reactive functional group containing at least one carbon-carbon double bond in the molecule. may be (A2-1) A compound that does not have hot melt properties as a whole molecule, has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and is SiO 4 / 2 and an organopolysiloxane resin fine particle containing siloxane units represented by the formula: (A2-2) A linear or branched organopolysiloxane that is liquid at 25°C and has a curing reactive functional group containing at least two carbon-carbon double bonds in the molecule. These components will be described below.
[0032] [Component (A1)] The component (A1) itself has hot melt properties and has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, so it is cured by the curing agent (C) described below. (A1) a resinous organopolysiloxane, (A2) an organopolysiloxane crosslinked product obtained by crosslinking at least one organopolysiloxane; (A3) a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block; Or a mixture of at least two of these The organopolysiloxane resin fine particles consisting of the above are preferred.
[0033] The (A1) component is a resinous organopolysiloxane having a hydrosilylation reactive group and / or a radical reactive group, and is preferably a hot-melt resinous organopolysiloxane having many T or Q units and an aryl group. Examples of such (A1) component include MQ resins, MDQ resins, MTQ resins, MDTQ resins, TD resins, TQ resins, and TDQ resins consisting of any combination of triorganosiloxy units (M units) (organo groups are methyl groups only, methyl groups and vinyl groups or phenyl groups), diorganosiloxy units (D units) (organo groups are methyl groups only, methyl groups and vinyl groups or phenyl groups), monoorganosiloxy units (T units) (organo groups are methyl groups, vinyl groups or phenyl groups), and siloxy units (Q units). The component (A1) has at least two hydrosilylation reactive groups and / or radical reactive groups in the molecule, and it is preferred that at least 10 mol % of all organic groups in the molecule are aryl groups, particularly phenyl groups.
[0034] Since the component (A2) is formed by crosslinking at least one organopolysiloxane, cracks are unlikely to occur when cured with the curing agent (C), and curing shrinkage can be reduced. Here, "crosslinking" refers to linking the organopolysiloxane, which is the raw material, to the organopolysiloxane through a hydrosilylation reaction, a condensation reaction, a radical reaction, a high-energy ray reaction, or the like. Examples of the hydrosilylation reactive group and the radical reactive group (including a high-energy ray reactive group) are the same as those described above, and examples of the condensation reactive group include a hydroxyl group, an alkoxy group, and an acyloxy group.
[0035] The units constituting the (A2) component are not limited, and examples thereof include siloxane units and silalkylene group-containing siloxane units. In addition, since sufficient hardness and mechanical strength are imparted to the resulting cured product, it is preferable that the same molecule contains a resinous polysiloxane unit and a chain-like polysiloxane unit. In other words, the (A2) component is preferably a crosslinked product of a resinous (resinous) organopolysiloxane and a chain-like (including linear or branched) organopolysiloxane. By introducing a resinous organopolysiloxane structure-chain-like organopolysiloxane structure into the (A2) component, the (A2) component exhibits good hot melt properties and also exhibits good curability due to the (C) curing agent.
[0036] The component (A2) is (1) A resin-like organopolysiloxane structure and a linear organopolysiloxane structure are linked by alkylene bonds in a molecule via a hydrosilylation reaction between an organopolysiloxane having at least two alkenyl groups per molecule and an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule. (2) At least two organopolysiloxanes having at least two radical reactive groups in one molecule are subjected to a radical reaction with an organic peroxide, resulting in a resinous organopolysiloxane structure and a linear organopolysiloxane structure linked in the molecule by a siloxane bond or an alkylene bond. (3) A resin-like organopolysiloxane structure and a linear organopolysiloxane structure are linked in the molecule through a siloxane (-Si-O-Si-) bond via a condensation reaction of at least two types of organopolysiloxane. Such component (A2) has a structure in which the resin structure and the organopolysiloxane portion of the chain structure are linked by an alkylene group or a new siloxane bond, thereby significantly improving the hot melt properties.
[0037] In the above (1) and (2), examples of the alkylene group contained in component (A2) include alkenyl groups having 2 to 20 carbon atoms, such as ethylene group, propylene group, butylene group, pentylene group, and hexylene group, which may be linear or branched, and are preferably ethylene or hexylene groups.
[0038] The crosslinked product of the resinous organopolysiloxane and the chain (including linear and branched) organopolysiloxane is composed, for example, of the following siloxane units and silalkylene group-containing siloxane units. M unit:R 1 R 2 2SiO 1 / 2 A siloxane unit represented by the formula: D unit:R 1 R 2 SiO 2 / 2 A siloxane unit represented by the formula: R 3 M / R 3 D unit:R 3 1 / 2 R 2 2SiO 1 / 2 and R 3 1 / 2 R 2 SiO 2 / 2 At least one siloxane unit selected from silalkylene group-containing siloxane units represented by the formula: T / Q unit:R 2 SiO 3 / 2 and SiO 4 / 2At least one siloxane unit selected from the siloxane units represented by
[0039] In the formula, R 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of these groups are the same as those mentioned above. 1 is preferably a methyl group, a vinyl group, or a phenyl group. However, among all the siloxane units, at least two R 1 is preferably an alkenyl group.
[0040] In addition, in the formula, R 2 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown in R 2 is preferably a methyl group or a phenyl group.
[0041] In addition, in the formula, R 3 is a linear or branched alkylene group having 2 to 20 carbon atoms bonded to a silicon atom in another siloxane unit. Examples of the alkylene group include the same groups as those mentioned above, and an ethylene group or a hexylene group is preferred.
[0042] The M unit is a siloxane unit constituting the terminal of the component (A2), and the D unit is a siloxane unit constituting a linear polysiloxane structure. It is preferable that an alkenyl group is present on the M unit or D unit, particularly on the M unit. 3 M units and R 3 The D unit is a siloxane unit that is bonded to a silicon atom in another siloxane unit via a silalkylene bond and to a silicon atom in another siloxane unit via an oxygen atom. The T / Q unit is a branched siloxane unit that gives the polysiloxane a resinous structure. The (A2) component is R 2 SiO3 / 2 and / or SiO 4 / 2 In particular, in order to improve the hot melt properties of the component (A2) and adjust the content of aryl groups in the component (A2), it is preferable that the component (A2) contains a siloxane unit represented by R 2 SiO 3 / 2 It is preferable that the siloxane unit represented by R 2 It is preferred that the siloxane unit contains a phenyl group.
[0043] R 3 M / R 3 The D unit is one of the characteristic structures of the (A2) component, and R 3 It represents a structure in which silicon atoms are bridged via an alkylene group of the formula: 3 1 / 2 R 2 2SiO 1 / 2 and an alkylene group-containing siloxane unit represented by R 3 1 / 2 R 2 SiO 2 / 2 Of all the siloxane units constituting component (A2), at least two are preferably alkylene group-containing siloxane units represented by the formula: 3 The preferred bond between the siloxane units having an alkylene group is as described above, and the bond between the two alkylene group-containing siloxane units is R 3 The number of is expressed as a bond valence of "1 / 2" like oxygen in the M unit. If R 3 If the number of is 1, then [O 1 / 2 R 2 2SiR 3 SiR 2 2O 1 / 2 ], [O 1 / 2 R 2 2SiR 3 SiR 2 O 2 / 2 ] and [O 2 / 2 R 2 SiR 3 SiR 2 O 2 / 2In component (A2), at least one selected from the structural units of siloxanes represented by the formula:] is contained, and each oxygen atom (O) is bonded to a silicon atom contained in the aforementioned M, D, or T / Q unit. By having such a structure, component (A2) can be relatively easily designed to have a structure in which a linear polysiloxane structure consisting of D units and a resinous polysiloxane structure containing T / Q units are contained within the molecule, and the physical properties of the component (A2) are remarkably excellent.
[0044] In the above (1), the compound can be obtained by subjecting an organopolysiloxane having at least two alkenyl groups per molecule and an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule to a hydrosilylation reaction in a reaction ratio such that [number of moles of alkenyl groups] / [number of moles of silicon-bonded hydrogen atoms]>1.
[0045] In the above (2), at least two types of organopolysiloxanes each having at least two radical reactive groups in one molecule can be obtained by radical reaction with an organic peroxide in an amount that is insufficient to react with all of the radical reactive groups in the system.
[0046] In the above (1) and (2), the component (A2) is a product of a hydrosilylation reaction or a radical reaction between an organopolysiloxane having a resinous siloxane structure and an organopolysiloxane having a chain siloxane structure.
[0047] For example, the component (A2) is (A R ) R in the molecule 2 SiO 3 / 2 (In the formula, R 2 is the same group as above.) and / or SiO 4 / 2 and having an alkenyl group having 2 to 20 carbon atoms, a silicon-bonded hydrogen atom, or a radical-reactive group; and (A L ) R in the molecule 2 2SiO2 / 2 A siloxane unit represented by the formula: 2 is the same group as above. R ) at least one linear organopolysiloxane having a group capable of hydrosilylation or radical reaction with component (a), the group being an alkenyl group having 2 to 20 carbon atoms or a silicon-bonded hydrogen atom, (A R ) component or (A L ) is an organopolysiloxane obtained by reacting the two components in a ratio designed so that the hydrosilylation reactive groups and / or radical reactive groups in the two components remain after the reaction.
[0048] In the above (1), (A R When at least a portion of the component (A) is a resinous organopolysiloxane having an alkenyl group having 2 to 20 carbon atoms, L It is preferable that at least a portion of the component (a) is a linear organopolysiloxane having silicon-bonded hydrogen atoms.
[0049] Similarly, (A R When at least a portion of component (A) is a resinous organopolysiloxane having silicon-bonded hydrogen atoms, L At least a portion of the ) component is preferably a chain organopolysiloxane having an alkenyl group having 2 to 20 carbon atoms.
[0050] Such an (A2) component is (a1) Component: 1-1 ) ingredients and / or the following (a 1-2 ) an organopolysiloxane having at least two alkenyl groups having 2 to 20 carbon atoms in the molecule, which is subjected to a radical reaction with an organic peroxide; or Component (a1), (a2) an organohydrogenpolysiloxane, It is preferable that the hydrosilylation reaction is carried out in the presence of a hydrosilylation catalyst such that the molar ratio of silicon-bonded hydrogen atoms in component (a2) is 0.2 to 0.7 mol per mol of alkenyl groups having 2 to 20 carbon atoms in component (a1).
[0051] (a 1-1 ) component is a polysiloxane having a relatively high amount of branched units and has the average unit formula: (R 4 3SiO 1 / 2 ) a (R 4 2SiO 2 / 2 ) b (R 4 SiO 3 / 2 ) c (SiO 4 / 2 ) d (R 5 O 1 / 2 ) e In the formula, R 4 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown in R 4 is preferably a methyl group, a vinyl group, or a phenyl group, provided that R 4 At least two of R are alkenyl groups. In addition, since the hot melt property is good, 4 Preferably, 10 mol % or more, or 20 mol % or more of R 5 is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and examples of the alkyl group include the same as those mentioned above.
[0052] In the formula, a is a number within the range of 0 to 0.7, b is a number within the range of 0 to 0.7, c is a number within the range of 0 to 0.9, d is a number within the range of 0 to 0.7, e is a number within the range of 0 to 0.1, and c+d is a number within the range of 0.3 to 0.9, and a+b+c+d is 1, and preferably a is a number within the range of 0 to 0.6, b is a number within the range of 0 to 0.6, c is a number within the range of 0 to 0.9, d is a number within the range of 0 to 0.5, e is a number within the range of 0 to 0.05, and c+d is a number within the range of 0.4 to 0.9, and a+b+c+d is 1. This is because when a, b, and c+d are each a number within the above range, the hardness and mechanical strength of the obtained cured product are excellent.
[0053] Such (a 1-1 ) component includes the following organopolysiloxanes: In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. (ViMe2SiO 1 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.75 (HO 1 / 2 ) 0.02 (ViMe2SiO 1 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.75 (ViMe2SiO 1 / 2 ) 0.20 (PhSiO 3 / 2 ) 0.80 (ViMe2SiO 1 / 2 ) 0.15 (Me3SiO 1 / 2 ) 0.38 (SiO 4 / 2 ) 0.47 (HO 1 / 2 ) 0.01 (ViMe2SiO 1 / 2 ) 0.13 (Me3SiO 1 / 2 ) 0.45 (SiO 4 / 2 ) 0.42 (HO 1 / 2 ) 0.01 (ViMe2SiO1 / 2 ) 0.15 (PhSiO 3 / 2 ) 0.85 (HO 1 / 2 ) 0.01 (MeSiO 2 / 2 ) 0.15 (MeViSiO 2 / 2 ) 0.10 (PhSiO 3 / 2 ) 0.75 (HO 1 / 2 ) 0.04 (MeViPhSiO 1 / 2 ) 0.20 (PhSiO 3 / 2 ) 0.80 (HO 1 / 2 ) 0.05 (ViMe2SiO 1 / 2 ) 0.15 (PhSiO 3 / 2 ) 0.75 (SiO 4 / 2 ) 0.10 (HO 1 / 2 ) 0.02 (Ph2SiO 2 / 2 ) 0.25 (MeViSiO 2 / 2 ) 0.30 (PhSiO 3 / 2 ) 0.45 (HO 1 / 2 ) 0.04 (Me3SiO 1 / 2 ) 0.20 (ViMePhSiO 1 / 2 ) 0.40 (SiO 4 / 2 ) 0.40 (HO 1 / 2 ) 0.08
[0054] (a 1-2 ) component is a polysiloxane having a relatively high amount of linear siloxane units and has the average unit formula: (R 4 3SiO 1 / 2 ) a' (R 4 2SiO 2 / 2 ) b' (R 4 SiO3 / 2 ) c' (SiO 4 / 2 ) d' (R 5 O 1 / 2 ) e' In the formula, R is an organopolysiloxane having at least two alkenyl groups having 2 to 20 carbon atoms in one molecule. 4 and R 5 is the same group as defined above.
[0055] In the formula, a' is a number within the range of 0.01 to 0.3, b' is a number within the range of 0.4 to 0.99, c' is a number within the range of 0 to 0.2, d' is a number within the range of 0 to 0.2, e' is a number within the range of 0 to 0.1, and c'+d' is a number within the range of 0 to 0.2, and a'+b'+c'+d' is 1, and preferably a' is a number within the range of 0.02 to 0.20, b' is a number within the range of 0.6 to 0.99, c' is a number within the range of 0 to 0.1, d' is a number within the range of 0 to 0.1, j' is a number within the range of 0 to 0.05, and c'+d' is a number within the range of 0 to 0.1, and a'+b'+c'+d' is 1. This is because when a', b', c', and d' are each numbers within the above ranges, toughness can be imparted to the obtained cured product.
[0056] Such (a 1-2 ) component includes the following organopolysiloxanes: In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. ViMe2SiO(MePhSiO) 18 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.10 (MePhSiO 2 / 2 ) 0.90 ViMe2SiO(MePhSiO) 30 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.063 (MePhSiO 2 / 2 ) 0.937 ViMe2SiO(MePhSiO) 150 SiMe2Vi, i.e. (ViMe2SiO1 / 2 ) 0.013 (MePhSiO 2 / 2 ) 0.987 ViMe2SiO(Me2SiO) 18 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.10 (MeSiO 2 / 2 ) 0.90 ViMe2SiO(Me2SiO) 30 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.063 (MeSiO 2 / 2 ) 0.937 ViMe2SiO(Me2SiO) 35 (MePhSiO) 13 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.04 (MeSiO 2 / 2 ) 0.70 (MePhSiO 2 / 2 ) 0.26 ViMe2SiO(Me2SiO) 10 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.17 (MeSiO 2 / 2 ) 0.83 (ViMe2SiO 1 / 2 ) 0.10 (MePhSiO 2 / 2 ) 0.80 (PhSiO 3 / 2 ) 0.10 (HO 1 / 2 ) 0.02 (ViMe2SiO 1 / 2 ) 0.20 (MePhSiO 2 / 2 ) 0.70 (SiO 4 / 2 ) 0.10 (HO 1 / 2 ) 0.01 HOMe2SiO(MeViSiO) 20 SiMe2OH Me2ViSiO(MePhSiO) 30SiMe2Vi Me2ViSiO(Me2SiO) 150 SiMe2Vi
[0057] (a 1-1 The component (a) is preferably used from the viewpoint of imparting hardness and mechanical strength to the resulting cured product. 1-2 Component (a2) can be added as an optional component from the viewpoint of imparting toughness to the obtained cured product, but when a crosslinking agent having many linear siloxane units is used in component (a2) below, it may be substituted therewith. In either case, the mass ratio of the component having many branched siloxane units to the component having many linear siloxane units is preferably within the range of 50:50 to 100:0, or within the range of 60:40 to 100:0. This is because when the mass ratio of the component having many branched siloxane units to the component having many linear siloxane units is within the above range, the hardness and mechanical strength of the obtained cured product are good.
[0058] In addition, when the component (a1) is subjected to a radical reaction with an organic peroxide, 1-1 ) component and (a 1-2 ) components in a ratio of 10:90 to 90:10, and it is possible to eliminate the need to use component (a2).
[0059] The component (a2) is a compound represented by the formula (a 1-1 ) component and / or (a 1-2 (a2) is a component for crosslinking component (a1) and is an organopolysiloxane containing at least two silicon-bonded hydrogen atoms in one molecule. Examples of groups bonded to silicon atoms other than hydrogen atoms in component (a2) include alkyl groups having 1 to 20 carbon atoms, halogen-substituted alkyl groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, halogen-substituted aryl groups having 6 to 20 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, alkoxy groups, epoxy-containing groups, and hydroxyl groups, and examples of such groups are the same as those mentioned above.
[0060] Although there are no limitations on such component (a2), it is preferable that the component (a2) has the average composition formula: R6 k H m SiO (4-k-m) / 2 In the formula, R 6 is an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, 1 Of these, a methyl group or a phenyl group is preferable.
[0061] In the formula, k is a number in the range of 1.0 to 2.5, and preferably a number in the range of 1.2 to 2.3, m is a number in the range of 0.01 to 0.9, and preferably a number in the range of 0.05 to 0.8, and k+m is a number in the range of 1.5 to 3.0, and preferably a number in the range of 2.0 to 2.7.
[0062] The component (a2) may be a resinous organohydrogenpolysiloxane having a large number of branched siloxane units, or a linear organohydrogenpolysiloxane having a large number of linear siloxane units. 2-1 ), an organohydrogenpolysiloxane represented by the following (a 2-2 ) or a mixture thereof.
[0063] (a 2-1 ) ingredients are average unit formula: [R 7 3SiO 1 / 2 ] f [R 7 2SiO 2 / 2 ] g [R 7 SiO 3 / 2 ] h [SiO 4 / 2 ] i (R 5 O 1 / 2 ) j In the formula, R 7 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or a hydrogen atom, 1 In addition, in the formula, R 5 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and examples thereof include the same groups as those mentioned above.
[0064] In the formula, f is a number in the range of 0 to 0.7, g is a number in the range of 0 to 0.7, h is a number in the range of 0 to 0.9, i is a number in the range of 0 to 0.7, j is a number in the range of 0 to 0.1, and h+i is a number in the range of 0.3 to 0.9, and f+g+h+i is 1, and preferably, f is a number in the range of 0 to 0.6, g is a number in the range of 0 to 0.6, h is a number in the range of 0 to 0.9, i is a number in the range of 0 to 0.5, j is a number in the range of 0 to 0.05, and h+i is a number in the range of 0.4 to 0.9, and f+g+h+i is 1.
[0065] (a 2-2 ) ingredients are average unit formula: (R 7 3SiO 1 / 2 ) f' (R 7 2SiO 2 / 2 ) g' (R 7 SiO 3 / 2 ) h' (SiO 4 / 2 ) i' (R 5 O 1 / 2 ) j' In the formula, R is an organopolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule. 7 and R 5 is the same group as defined above.
[0066] Furthermore, in the formula, f' is a number in the range of 0.01 to 0.3, g' is a number in the range of 0.4 to 0.99, h' is a number in the range of 0 to 0.2, i' is a number in the range of 0 to 0.2, j' is a number in the range of 0 to 0.1, and h'+i' is a number in the range of 0 to 0.2, and f'+g'+h'+i' is 1, and preferably f' is a number in the range of 0.02 to 0.20, g' is a number in the range of 0.6 to 0.99, h' is a number in the range of 0 to 0.1, i' is a number in the range of 0 to 0.1, j' is a number in the range of 0 to 0.05, and h'+i' is a number in the range of 0 to 0.1, and f'+g'+h'+i' is 1.
[0067] As described above, in the component (a2), the resin-like organopolysiloxane having a large number of branched siloxane units imparts hardness and mechanical strength to the cured product, while the resulting organopolysiloxane having a large number of linear siloxane units imparts toughness to the cured product. 2-1 ) component and (a 2-2 Specifically, when the branched siloxane unit is small in the (a1) component, it is preferable to use (a 2-1 It is preferable to mainly use component (a1), and when the amount of linear siloxane units in component (a1) is small, it is preferable to mainly use component (a 2-2 It is preferable to mainly use the component (a2). 2-1 ) component and (a 2-2 ) The mass ratio of the components is preferably within the range of 50:50 to 100:0, or 60:40 to 100:0.
[0068] An example of such component (a2) is the following organopolysiloxane: In the formula, Me and Ph represent a methyl group and a phenyl group, respectively. Ph2Si(OSiMe2H)2, i.e., Ph 0.67 Me 1.33 H 0.67 SiO 0.67 HMe2SiO(Me2SiO) 20 SiMe2H, i.e., Me 2.00 H 0.09 SiO 0.95 HMe2SiO(Me2SiO) 55 SiMe2H, i.e., Me 2.00 H 0.04 SiO 0.98 PhSi(OSiMe2H)3, i.e., Ph 0.25 Me 1.50 H 0.75 SiO 0.75 (HMeSiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4 , i.e., Ph 0.40 Me 1.20 H 0.60 SiO 0.90
[0069] The amount of component (a2) added is an amount such that the molar ratio of silicon-bonded hydrogen atoms in component (a2) to the alkenyl groups in component (a1) is 0.2 to 0.7, and preferably 0.3 to 0.6, because when the amount of component (a2) added is within the above range, the initial hardness and mechanical strength of the resulting cured product are good.
[0070] The organic peroxide used for the radical reaction of the component (a1) is not limited, and the organic peroxides exemplified in the component (C) below can be used. 1-1 ) component and (a 1-2 It is preferable that the mass ratio of the (a1) components is within the range of 10:90 to 90:10. The amount of the organic peroxide added is not limited, but is preferably within the range of 0.1 to 5 parts by mass, 0.2 to 3 parts by mass, or 0.2 to 1.5 parts by mass, per 100 parts by mass of the (a1) component.
[0071] The hydrosilylation catalyst used to subject the components (a1) and (a2) to the hydrosilylation reaction is not limited, and any of the hydrosilylation catalysts exemplified for component (C) below can be used. The amount of the hydrosilylation catalyst added is preferably such that the platinum-based metal atom in the hydrosilylation catalyst is, by mass unit, within the range of 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm relative to the total amount of components (a1) and (a2).
[0072] The above (A3) is obtained by subjecting the following component (a3) and the following component (a4) to a condensation reaction in the presence of a condensation reaction catalyst.
[0073] (a3) The component has the average unit formula: (R 8 3SiO 1 / 2 ) p (R 8 2SiO 2 / 2 ) q (R 8 SiO 3 / 2 ) r (SiO 4 / 2 ) s (R 9 O 1 / 2 ) t In the formula, R 8 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of these groups are the same as those mentioned above. 9 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an acyl group having 2 to 5 carbon atoms, and examples of such groups include alkoxy groups such as methoxy and ethoxy groups, and acyloxy groups. Component (a3) has at least one silicon-bonded hydroxyl group, silicon-bonded alkoxy group, or silicon-bonded acyloxy group in each molecule. In addition, at least two R 8 is an alkenyl group, and all R 8It is preferable that 10 mol % or more, or 20 mol % or more of these groups are phenyl groups.
[0074] In the formula, p is a number within the range of 0 to 0.7, q is a number within the range of 0 to 0.7, r is a number within the range of 0 to 0.9, s is a number within the range of 0 to 0.7, t is a number within the range of 0.01 to 0.10, and r+s is a number within the range of 0.3 to 0.9, and p+q+r+s is 1, and preferably, p is a number within the range of 0 to 0.6, q is a number within the range of 0 to 0.6, r is a number within the range of 0 to 0.9, s is a number within the range of 0 to 0.5, t is a number within the range of 0.01 to 0.05, and r+s is a number within the range of 0.4 to 0.9. This is because, when p, q, and r+s are each a number within the above range, a hot-melt silicone can be obtained that has flexibility at 25°C, is non-fluid, has low surface tack, and has a sufficiently low melt viscosity at high temperatures.
[0075] (a4) The component has the average unit formula: (R 8 3SiO 1 / 2 ) p' (R 8 2SiO 2 / 2 ) q' (R 8 SiO 3 / 2 ) r' (SiO 4 / 2 ) s' (R 9 O 1 / 2 ) t' In the formula, R 8 and R 9is the same group as above. Component (a4) has at least one silicon-bonded hydroxyl group, silicon-bonded alkoxy group, or silicon-bonded acyloxy group in one molecule. In the formula, p' is a number in the range of 0.01 to 0.3, q' is a number in the range of 0.4 to 0.99, r' is a number in the range of 0 to 0.2, s' is a number in the range of 0 to 0.2, t' is a number in the range of 0 to 0.1, and r'+s' is a number in the range of 0 to 0.2, and p'+q'+r'+s' is 1, and preferably p' is a number in the range of 0.02 to 0.20, q' is a number in the range of 0.6 to 0.99, r' is a number in the range of 0 to 0.1, s' is a number in the range of 0 to 0.1, t' is a number in the range of 0 to 0.05, and r'+s' is a number in the range of 0 to 0.1. This is because, when p', q', r', and s' are each numbers within the above ranges, a hot-melt silicone can be obtained that has flexibility at 25°C, yet is non-flowable, has low surface tack, and has a sufficiently low melt viscosity at high temperatures.
[0076] The condensation reaction catalyst for the condensation reaction of the components (a3) and (a4) is not limited, and examples thereof include organotin compounds such as dibutyltin dilaurate, dibutyltin diacetate, tin octenate, dibutyltin dioctate, and tin laurate; organotitanium compounds such as tetrabutyl titanate, tetrapropyl titanate, and dibutoxybis(ethylacetoacetate); acidic compounds such as hydrochloric acid, sulfuric acid, and dodecylbenzenesulfonic acid; alkaline compounds such as ammonia and sodium hydroxide; and amine compounds such as 1,8-diazabicyclo[5.4.0]undecene (DBU) and 1,4-diazabicyclo[2.2.2]octane (DABCO). Of these, organotin compounds and organotitanium compounds are preferred.
[0077] The component (A3) is a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block. The component (A3) preferably contains 40 to 90 mol % of a compound represented by the formula [R 1 2SiO 2 / 2 10 to 60 mol % of disiloxy units of the formula [R 1 SiO 3 / 2It is preferable that the trisiloxy unit is composed of the above-mentioned trisiloxy unit [≡SiOH] and contains 0.5 to 35 mol % of silanol groups [≡SiOH]. 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of which are the same as those mentioned above. 1 is an alkenyl group. 1 2SiO 2 / 2 ] forms linear blocks having an average of 100 to 300 disiloxy units per linear block, and the trisiloxy units [R 1 SiO 3 / 2 ] is a resinous organosiloxane block copolymer having a weight average molecular weight of at least 20,000 g / mole and containing 0.5-4.5 mol % of at least one alkenyl group, wherein at least 30% of the non-linear blocks are bonded to each other and each linear block is bonded to at least one non-linear block via a -Si-O-Si- bond, and wherein the resinous organosiloxane block copolymer has a weight average molecular weight of at least 20,000 g / mole and contains 0.5-4.5 mol % of at least one alkenyl group.
[0078] The component (A3) is prepared by a condensation reaction of (a5) a resinous organosiloxane or a resinous organosiloxane block copolymer, (a6) a linear organosiloxane, and, if necessary, (a7) a siloxane compound.
[0079] (a5) The component has the average unit formula: [R 1 2R 2 SiO 1 / 2 ] i [R 1 R 2 SiO 2 / 2 ] ii [R 1 SiO 3 / 2 ] iii [R 2 SiO 3 / 2 ] iv [SiO 4 / 2 ] v In the formula, R 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of the same groups as those mentioned above are given. 2 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown below.
[0080] In the formula, i, ii, iii, iv, and v represent the mole fraction of each siloxy unit, where i is a number from 0 to 0.6, ii is a number from 0 to 0.6, iii is a number from 0 to 1, iv is a number from 0 to 1, and v is a number from 0 to 0.6, with the proviso that ii+iii+iv+v>0 and i+ii+iii+iv+v≦1. In addition, the component (a5) preferably contains 0 to 35 mol % of silanol groups [≡SiOH] in one molecule.
[0081] The component (a6) has the general formula: R 1 3-α (X) α SiO(R 1 2SiO) β Si(X) α R 1 3-α In the formula, R 1 is the same as above, and examples thereof include the same groups as above. 5 , F, Cl, Br, I, -OC(O)R 5 , -N(R 5 )2, or -ON=CR 5 2 (where R 5is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.) In the formula, each α is independently 1, 2, or 3, and β is an integer of 50 to 300.
[0082] The component (a7) has the general formula: R 1 R 2 2SiX In the formula, R 1 , R 2 and X are the same groups as defined above.
[0083] The condensation reaction catalyst for the condensation reaction of component (a5) with component (a6) and / or component (a7) is not limited, and examples thereof include organic tin compounds such as dibutyltin dilaurate, dibutyltin diacetate, tin octenate, dibutyltin dioctate, and tin laurate; organic titanium compounds such as tetrabutyl titanate, tetrapropyl titanate, and dibutoxybis(ethylacetoacetate); acidic compounds such as hydrochloric acid, sulfuric acid, and dodecylbenzenesulfonic acid; alkaline compounds such as ammonia and sodium hydroxide; and amine compounds such as 1,8-diazabicyclo[5.4.0]undecene (DBU) and 1,4-diazabicyclo[2.2.2]octane (DABCO).
[0084] Component (A1) exhibits hot melt properties, specifically, it is non-flowable at 25°C and preferably has a melt viscosity at 100°C of 8000 Pa s or less. Non-flowable means that it does not flow under no load, and indicates, for example, a state below the softening point measured by the ring and ball method for testing the softening point of hot melt adhesives as specified in JIS K 6863-1994 "Testing Method for Softening Point of Hot Melt Adhesives". In other words, to be non-flowable at 25°C, the softening point must be higher than 25°C.
[0085] The melt viscosity of component (A1) at 100°C is preferably 8000 Pa s or less, 5000 Pa s or less, or in the range of 10 to 3000 Pa s. When the melt viscosity at 100°C is within the above range, good adhesion is achieved after cooling to 25°C after hot melting.
[0086] The particle size of the component (A1) is not limited so long as it is in the form of fine particles, but the average primary particle size is preferably within the range of 1 to 5000 μm, 1 to 500 μm, 1 to 100 μm, 1 to 20 μm, or 1 to 10 μm. This average primary particle size can be determined, for example, by observation with an optical microscope or SEM. The shape of the component (A1) is not limited, and examples include spherical, spindle-shaped, plate-shaped, needle-shaped, and irregular shapes. Since it melts uniformly, it is preferable that the component (A1) is spherical or true spherical. In particular, by making the component (A1) true spherical with a size of 1 to 10 μm, the melting properties of the compound and the mechanical properties after curing can be favorably improved. .
[0087] The method for producing the (A1) component is not limited, and a known method can be used. For example, the (A1) component can be simply microparticulated, or the step of crosslinking at least two types of organopolysiloxane and the step of microparticulating the reaction product can be carried out simultaneously or separately. When obtaining the (A1) component in microparticulate form, a part of the (C) component described below, such as a hydrosilylation reaction catalyst, can be microparticulated together with the (A1) component, and this is preferable.
[0088] After crosslinking at least two kinds of organopolysiloxanes, the organopolysiloxane obtained can be pulverized by a pulverizer or directly pulverized in the presence of a solvent. The pulverizer is not limited, and examples thereof include a roll mill, a ball mill, a jet mill, a turbo mill, and a planetary mill. In addition, examples of the method for directly pulverizing the silicone in the presence of a solvent include spraying by a spray dryer, or pulverization by a two-screw kneader or a belt dryer. In the present invention, it is particularly preferable to use the spherical hot-melt organopolysiloxane resin fine particles obtained by spraying by a spray dryer from the viewpoints of the melting properties of the granular compound, the flexibility of the cured product, the amount of the (B) component blended, the efficiency during production, and the handling and workability of the composition.
[0089] By using a spray dryer or the like, it is possible to produce component (A1) that is spherical and has an average primary particle size of 1 to 500 μm. The heating and drying temperature of the spray dryer must be appropriately set based on the heat resistance of the organopolysiloxane resin fine particles. In order to prevent secondary aggregation of the organopolysiloxane resin fine particles, it is preferable to control the temperature of the organopolysiloxane resin fine particles to a temperature equal to or lower than their glass transition temperature. The organopolysiloxane resin fine particles thus obtained can be collected using a cyclone, bag filter, or the like.
[0090] In order to obtain a uniform (A1) component, a solvent may be used in the above step within a range that does not inhibit the curing reaction. The solvent is not limited, but examples thereof include aliphatic hydrocarbons such as n-hexane, cyclohexane, and n-heptane; aromatic hydrocarbons such as toluene, xylene, and mesitylene; ethers such as tetrahydrofuran and dipropyl ether; silicones such as hexamethyldisiloxane, octamethyltrisiloxane, and decamethyltetrasiloxane; esters such as ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.
[0091] [(A2-1) component] The component (A2-1) is one of the main components of the composition used together with the component (A2-2), and is an organopolysiloxane resin fine particle containing a curing reactive functional group that does not have hot melt properties by itself, or a mixture of organopolysiloxane resin fine particles containing the same. Such a component (A2-1) must be in the form of fine particles together with other components (for example, the component (A2-2) which is a linear or branched organopolysiloxane, the component (A2-1-1) which is a non-reactive organopolysiloxane resin fine particle, and the component (C) which is a curing agent), and is particularly preferably a spherical silicone fine particle with an average primary particle diameter of 1 to 20 μm.
[0092] The component (A2-1) must have a curing reactive group that has a carbon-carbon double bond in the molecule. Such a curing reactive group is a hydrosilylation-reactive, radical-reactive, or organic peroxide-curable functional group that forms a cured product through a crosslinking reaction with other components.
[0093] The (A2-1) component is an organopolysiloxane resin fine particle that does not have hot melt properties as a whole molecule and is solid in a solvent-free state. Here, not having hot melt properties means that the resin particles of the (A2-1) component do not show heat melting behavior at a temperature of 200°C or less by themselves, specifically, that it does not have a softening point and melt viscosity. In the (A2-1) component, such physical properties are not particularly limited structurally, but it is preferable that the functional group in the organopolysiloxane resin is a monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly a functional group selected from an alkyl group and an alkenyl group having 1 to 10 carbon atoms such as a methyl group, and does not substantially contain an aryl group such as a phenyl group. If a large amount of phenyl groups or the like is contained, the component may have hot melt properties, and the color resistance of the cured product under heat aging (high temperature) described later may decrease. Preferably, the functional groups bonded to silicon atoms in component (A2-1) are selected from alkenyl groups such as methyl and vinyl, and it is preferred that 70 to 99 mol% of all functional groups bonded to silicon atoms are methyl, more preferably 80 to 99 mol%, and particularly preferably 88 to 99 mol% are methyl, and the remaining functional groups bonded to silicon atoms are alkenyl groups such as vinyl. In this range, component (A2-1) can be designed as a component that is not hot-melt, but is particularly excellent in the color resistance of the cured product at high temperatures. Note that component (A2-1) may contain a small amount of hydroxyl or alkoxy groups.
[0094] The component (A2-1) is a solid organopolysiloxane resin fine particle in a solvent-free state, and contains SiO 4 / 2The branched siloxane units are preferably at least 40 mol % or more of the total siloxane units, more preferably at least 50 mol %, and particularly preferably in the range of 50 to 90 mol %. R is a monovalent organic group, preferably a functional group selected from monovalent hydrocarbon groups having 1 to 10 carbon atoms, particularly alkyl and alkenyl groups having 1 to 10 carbon atoms such as methyl groups, and from the viewpoint of technical effect, it is preferable that R does not substantially contain aryl groups such as phenyl groups.
[0095] That is, the component (A2-1) is preferably (A2-1-1) The molecule as a whole does not have hot melt properties, does not have a curing reactive functional group containing a carbon-carbon double bond in the molecule, and is not SiO 4 / 2 The organopolysiloxane resin fine particles may contain siloxane units represented by the following formula (1) in an amount of at least 20 mol % based on the total siloxane units.
[0096] Similarly, the component (A2-1) is preferably a copolymer of the above-mentioned component (A2-1-1) and the component (A2-1-2) which does not have hot melt properties as a whole molecule, has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and is preferably a copolymer of the above-mentioned component (A2-1-2) and has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule. 4 / 2 The organopolysiloxane resin fine particle mixture may be composed of organopolysiloxane resin fine particles containing siloxane units represented by the following formula (I) in an amount of at least 20 mol % based on the total siloxane units.
[0097] [(A2-1-1) component] The component (A2-1-1) of the present invention is non-hot melt organopolysiloxane resin fine particles that do not have a curing reactive functional group that contains a carbon-carbon double bond in the molecule.
[0098] The component (A2-1-1) does not have hot melt properties as a whole molecule, does not have a curing reactive functional group containing a carbon-carbon double bond in the molecule, and is SiO 4 / 2The component (A2-1) is an organopolysiloxane resin fine particle containing siloxane units represented by the formula (I) in an amount of at least 20 mol % or more of all siloxane units. When this component is used as part of component (A2-1) in combination with the linear or branched organopolysiloxane, component (A2-2), in a prescribed quantitative range, this component provides hot melt properties for the composition as a whole.
[0099] The component (A2-1-1) is an organopolysiloxane resin fine particle that does not have hot melt properties as a whole molecule and is solid in a solvent-free state. Here, not having hot melt properties means that the resin particles of the component (A2-1-1) do not show heat melting behavior at temperatures of 200°C or less by themselves, specifically, that they do not have a softening point or melt viscosity, as already explained for the component (A2-1).
[0100] Preferably, the functional groups bonded to silicon atoms in component (A2-1-1) are methyl groups, and it is preferable that 70 mol% or more of all functional groups bonded to silicon atoms are methyl groups, more preferably 80 mol% or more are methyl groups, and particularly preferably 88 mol% or more are methyl groups. Within this range, component (A) can be designed as a component that is not hot-melt-like, but is particularly excellent in the color resistance of the cured product at high temperatures. Note that component (A) may contain a small amount of hydroxyl groups or alkoxy groups.
[0101] The component (A2-1-1) does not itself form a cured product because it does not have a curing reactive group that has a carbon-carbon double bond in the molecule. However, it has an effect of improving the hot melt properties of the composition as a whole and reinforcing the cured product, and can be used as part of the curable component (A2-1).
[0102] The component (A2-1-1) is a solid organopolysiloxane resin fine particle in a solvent-free state, and contains branched siloxane units, SiO 4 / 2The siloxane unit represented by the formula (1) is contained in an amount of at least 20 mol % of all siloxane units. The amount of the siloxane unit is preferably at least 40 mol % of all siloxane units, more preferably at least 50 mol %, and particularly preferably in the range of 50 to 65 mol %.
[0103] Preferably, the component (A2-1-1) is (A1) a copolymer having the following average unit formula: (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 SiO 3 / 2 ) c (SiO 4 / 2 ) d (R 2 O 1 / 2)e (In the formula, each R 1 are independently monovalent hydrocarbon radicals having 1 to 10 carbon atoms and no carbon-carbon double bonds; each R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; a, b, c, d, and e are numbers that satisfy the following: 0.10≦a≦0.60, 0≦b≦0.70, 0≦c≦0.80, 0.20≦d≦0.65, 0≦e≦0.05, and a+b+c+d=1). The non-hot melt organopolysiloxane resin particles are represented by the formula:
[0104] In the above average unit formula, each R 1 are independently monovalent hydrocarbon radicals having 1 to 10 carbon atoms and no carbon-carbon double bonds, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, or similar alkyl radicals; phenyl, tolyl, xylyl, or similar aryl radicals; benzyl, phenethyl, or similar aralkyl radicals; and chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, or similar halogenated alkyl radicals, where the total R 1It is preferable that 70 mol % or more of R are alkyl groups having 1 to 10 carbon atoms such as methyl groups, and it is particularly preferable that 88 mol % or more of R are methyl groups from the viewpoint of industrial production and the technical effect of the invention. 1 It is preferable that the component (A) is substantially free of aryl groups such as phenyl groups. If the component (A) contains a large amount of aryl groups such as phenyl groups, the component (A) itself may become hot-melt, making it impossible to achieve the technical effects of the present invention, and the color resistance of the cured product at high temperatures may deteriorate.
[0105] In the formula, R 2 R is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. 2 The alkyl group of R is exemplified by methyl, ethyl, propyl, butyl, pentyl, or hexyl. 2 Functional group R containing 2 O 1 / 2 corresponds to the hydroxyl group or alkoxy group in the component (A2-1-1).
[0106] In the formula, a represents the general formula: R 1 3SiO 1 / 2 a is a number indicating the proportion of siloxane units. This number satisfies 0.1≦a≦0.60, and preferably 0.15≦a≦0.55. When a is equal to or greater than the lower limit of the above range, a composition containing this component can achieve good hot melt performance as a whole composition. On the other hand, when a is equal to or less than the upper limit of the above range, the mechanical strength (hardness, etc.) of the obtained cured product is not too low.
[0107] In the formula, b represents the general formula: R 1 2SiO 2 / 2 b is a number indicating the proportion of siloxane units. This number satisfies 0≦b≦0.70, and preferably 0≦b≦0.60. When b is equal to or less than the upper limit of the range, the composition containing this component can achieve good hot melt performance as a whole composition, and can obtain a granular composition that is less sticky at room temperature. In the present invention, b may be 0, and is preferred.
[0108] In the formula, c represents a group represented by the general formula: R 1 SiO 3 / 2c is a number indicating the proportion of siloxane units. This number satisfies 0≦c≦0.70, and preferably 0≦c≦0.60. When c is equal to or less than the upper limit of the range, the composition containing this component can achieve good hot melt performance as a whole composition, and can obtain a granular composition that is less sticky at room temperature. In the present invention, c may be 0, and is preferred.
[0109] In the formula, d is SiO 4 / 2 It is necessary that d is 0.20≦d≦0.65, preferably 0.40≦d≦0.65, and particularly preferably 0.50≦d≦0.65. Within this numerical range, a composition containing this component can achieve good hot melt performance as a whole composition, excellent mechanical strength of the resulting cured product, and a composition that is not sticky as a whole and has good handling and workability can be realized.
[0110] In the formula, e represents the general formula: R 2 O 1 / 2 e is a number indicating the proportion of units, which means a hydroxyl group or an alkoxy group bonded to a silicon atom that may be contained in the organopolysiloxane resin. This number satisfies 0≦e≦0.05, preferably 0≦e≦0.03. If e is equal to or less than the upper limit of the range, a material that realizes good hot melt performance as a whole composition can be obtained. In addition, the sum of a, b, c, and d, which are the sums of each siloxane unit, is ultimately equal to 1.
[0111] The component (A2-1-1) is a particulate organopolysiloxane resin having the above characteristics, and is preferably a spherical organopolysiloxane resin particulate having an average primary particle diameter of 1 to 20 μm as measured by a laser diffraction / scattering method or the like. By using such a particulate component, the present composition can be prepared or produced as a curable particulate composition having excellent handling and hot melt properties. The method for producing the component (A2-1-1) is not limited, and includes the same methods as those exemplified for the component (A1) above. In addition, when obtaining the particulate component (A2-1-1), the component (C) described below, for example, a hydrosilylation reaction catalyst, etc. may be particulated together with the component (A2-1-1), and this is preferable.
[0112] When the component (A2-1) of the present invention is a mixture containing a non-reactive component (A2-1-1), it is preferable to blend reactive organopolysiloxane resin fine particles in an amount of 3 to 50 parts by mass per 100 parts by mass of the component (A2-1-1).
[0113] More specifically, the component (A2-1) of the present invention is (A2-1-1) The molecule as a whole does not have hot melt properties, does not have a curing reactive functional group containing a carbon-carbon double bond in the molecule, and is not SiO 4 / 2 100 parts by mass of organopolysiloxane resin fine particles containing at least 20 mol % or more of siloxane units represented by the formula: (A2-1-2) A compound that does not have hot melt properties as a whole molecule, has a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and is SiO 4 / 2 3 to 50 parts by mass of organopolysiloxane resin fine particles containing siloxane units represented by the formula: A mixture of the following is particularly preferred.
[0114] [(A2-2) component] Component (A2-2) is one of the main components of the composition used together with component (A2-1), and is a linear or branched organopolysiloxane that is liquid at 25° C. and has a curing reactive functional group containing at least two carbon-carbon double bonds in the molecule. When mixed with the above-mentioned solid organopolysiloxane resin particles, this type of curing reactive chain organopolysiloxane exhibits hot melt properties in the entire composition.
[0115] Like the (A2-1) component, the (A2-2) component must have a curing reactive group having a carbon-carbon double bond in the molecule. Such a curing reactive group is a functional group that is hydrosilylation reactive, radical reactive, or organic peroxide curable, and forms a cured product by a crosslinking reaction with other components. Such a curing reactive group is an alkenyl group or an acrylic group, and examples thereof include the same groups as those described above, and in particular, a vinyl group or a hexenyl group is preferable.
[0116] Component (A2-2) is a linear or branched organopolysiloxane that is liquid at 25°C (room temperature), and when mixed with component (A2-1), which is solid at room temperature, and optionally with component (A2-1-2), which will be described later, the composition as a whole exhibits hot melt properties. Its structure is a small number of branched siloxane units (for example, the general formula: R 4 SiO 3 / 2 T units (R 4 are independently monovalent hydrocarbon radicals having 1 to 10 carbon atoms) or SiO 4 / 2 The organopolysiloxane may be a branched organopolysiloxane having a Q unit represented by the formula: (A2-2-1) The following structural formula: R 4 3SiO(SiR 4 2O) k SiR 4 3 (In the formula, each R 4 are independently monovalent hydrocarbon groups having 1 to 10 carbon atoms, provided that R 4 at least two of the groups are alkenyl groups, and k is a number from 20 to 5,000. It is a linear diorganopolysiloxane represented by the following formula: Preferably, it is a linear diorganopolysiloxane having one alkenyl group at each of both ends of the molecular chain.
[0117] In the formula, each R 4 are independently monovalent hydrocarbon radicals having 1 to 10 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, or similar alkyl groups; vinyl, allyl, butenyl, pentenyl, hexenyl, or similar alkenyl groups; phenyl, tolyl, xylyl, or similar aryl groups; benzyl, phenethyl, or similar aralkyl groups; and chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, or similar halogenated alkyl groups. 4 At least two of R are alkenyl groups, preferably vinyl groups. 4 is preferably a functional group selected from an alkyl group having 1 to 10 carbon atoms, such as a methyl group, and an alkenyl group, such as a vinyl group or a hexenyl group, and all of R 4 At least two of R are alkenyl groups, and the remaining R 4 From the viewpoint of the technical effect of the invention, it is preferable that R 4 It is preferable that R is substantially free of aryl groups such as phenyl groups. If it contains a large amount of aryl groups such as phenyl groups, the color resistance of the cured product at high temperatures may deteriorate. Particularly preferably, R has an alkenyl group such as a vinyl group at each end of the molecular chain and other R 4 is preferably a methyl group.
[0118] In the formula, k is a number of 20 to 5,000, preferably 30 to 3,000, and particularly preferably 45 to 800. When k is equal to or greater than the lower limit of the above range, a granular composition with little stickiness at room temperature can be obtained. On the other hand, when k is equal to or less than the upper limit of the above range, the composition as a whole can achieve good hot melt performance.
[0119] [Mixture containing non-hot melt organopolysiloxane resin fine particles] When the above-mentioned (A2-1-2) component, (A2-1-1) component and (A2-2) component are used as the (A) component of the present invention, the amount of the (A2-1-2) component used is within the range of 3 to 50 parts by mass, and particularly preferably within the range of 4 to 45 parts by mass, per 100 parts by mass of the (A2-1-1) component. Here, the (A2-1-2) component is a component that imparts curing reactivity to the present silicone composition together with the (A2-2) component, so that if it is less than the lower limit, the curing property and curing speed may decrease. On the other hand, if it exceeds the upper limit, the technical effect of high stress relaxation of the cured product may not be achieved, particularly when a large amount of functional filler is blended into the composition.
[0120] The combination of the above (A2-1-1,2) and (A2-2) components is not limited, but it is preferable to select a combination in which the molecular weight of the (A2-1-1,2) component, which is an organopolysiloxane resin particle, and the (A2-2) component, which is a linear or branched organopolysiloxane, are different. That is, a combination of a relatively small molecular weight (A2-1-1,2) component and a relatively large molecular weight (A2-2) component; or a combination of a relatively large molecular weight (A2-1-1,2) component and a relatively small molecular weight (A2-2) component is preferable from the viewpoint of particle formation. On the other hand, when components with relatively small molecular weights are combined, the two may be miscible with each other and may not be able to be particle formed. In addition, in the combination of a high molecular weight MQ resin and a high molecular weight (long chain) vinyl polysiloxane disclosed in Patent Document 3, the melt viscosity of the mixture tends to be high, and in the composition of the present invention to which a functional inorganic filler described later is added, it is necessary to reduce the amount of inorganic filler to be filled in order to produce a composition with a low melt viscosity.
[0121] [(B) Component] The (B) component of the present invention is a functional inorganic filler, and is preferably at least one type of filler that does not have a softening point or does not soften at 50°C or lower, and may be a component that improves the handling and workability of the composition and imparts mechanical properties and other properties to the cured product of the composition. Examples of the (B) component include inorganic fillers, organic fillers, and mixtures thereof, and inorganic fillers are preferred. Examples of the inorganic filler include reinforcing fillers, white pigments, thermally conductive fillers, conductive fillers, phosphors, and mixtures of at least two of these, and it is particularly preferred to contain a reinforcing filler that is substantially free of coarse particles having an average particle size of 5 μm or more. Examples of the organic filler include silicone resin-based fillers, fluororesin-based fillers, and polybutadiene resin-based fillers. The shape of these fillers is not particularly limited, and may be spherical, spindle-shaped, flat, needle-shaped, amorphous, etc.
[0122] When the present composition is used for applications such as a sealant, a protective agent, an adhesive, or a light reflector, it is preferable to incorporate a reinforcing filler as component (B) in order to impart mechanical strength to the cured product and improve protectiveness or adhesiveness. Examples of the reinforcing filler include fumed silica, precipitated silica, fused silica, calcined silica, fumed titanium dioxide, quartz, calcium carbonate, diatomaceous earth, aluminum oxide, aluminum hydroxide, zinc oxide, and zinc carbonate. In addition, these reinforcing fillers may be surface-treated with organoalkoxysilanes such as methyltrimethoxysilane; organohalosilanes such as trimethylchlorosilane; organosilazanes such as hexamethyldisilazane; siloxane oligomers such as α,ω-silanol-group-blocked dimethylsiloxane oligomers, α,ω-silanol-group-blocked methylphenylsiloxane oligomers, and α,ω-silanol-group-blocked methylvinylsiloxane oligomers. Furthermore, as a reinforcing filler, fibrous fillers such as calcium metasilicate, potassium titanate, magnesium sulfate, sepiolite, zonolite, aluminum borate, rock wool, and glass fiber may be used.
[0123] In particular, from the viewpoint of imparting good gap-filling properties to the present composition when melted, it is preferable that component (B) is a mixture of (b1) an inorganic filler having an average particle size of 0.1 μm or less, preferably a reinforcing filler, and (b2) an inorganic filler having an average particle size of 0.1 to 5.0 μm, preferably a reinforcing filler. The blending ratio of the two is arbitrary, but may be a mass ratio of 1 / 99 to 20 / 80, 1 / 99 to 50 / 50, or 5 / 95 to 40 / 60. In particular, (b1-1) fumed silica having an average particle size of 0.1 μm or less, preferably 0.05 μm or less, and (b2-1) fused silica having an average particle size of 0.1 to 5.0 μm, preferably 0.15 to 4.0 μm, may be contained in a ratio of 1 / 99 to 20 / 80, preferably 1 / 99 to 50 / 50, more preferably 5 / 95 to 40 / 60 by mass. When the particles of the mixture of inorganic fillers are the same or smaller in size as the particle size of component (A), a good silicone-filler matrix can be formed when melted. This improves the flexibility and mechanical strength of the cured product. In addition, since such component (B) does not substantially contain coarse particles, good gap-filling properties can also be achieved.
[0124] The curable granular silicone composition of the present invention can be used as a light reflector, particularly a light reflector for use in optical semiconductors (LEDs), and can impart whiteness to the cured product and improve light reflectivity, so a white pigment may be used as component (B). Examples of the white pigment include metal oxides such as titanium oxide, aluminum oxide, zinc oxide, zirconium oxide, and magnesium oxide; hollow fillers such as glass balloons and glass beads; and other materials such as barium sulfate, zinc sulfate, barium titanate, aluminum nitride, boron nitride, and antimony oxide. Titanium oxide is preferred because of its high light reflectance and hiding power. Aluminum oxide, zinc oxide, and barium titanate are preferred because of their high light reflectance in the UV region. The white pigment may also be surface-treated with a silane coupling agent, silica, aluminum oxide, or the like. A particularly suitable white pigment is titanium oxide fine particles having an average particle diameter of 0.5 μm or less. Filling the composition with about 10 to 30% by volume imparts high light reflectance and hiding power to the cured product in the visible wavelength range, and further has the practical benefit of showing almost no change in light reflectance in the visible wavelength range when comparing the low wavelength side and the high wavelength side.
[0125] Component (B) may contain silicone fine particles that do not fall under component (A), and can improve or, if desired, adjust stress relaxation properties, etc. Examples of silicone fine particles include non-reactive silicone resin fine particles and silicone elastomer fine particles, with silicone elastomer fine particles being a suitable example from the standpoint of improving flexibility or stress relaxation properties.
[0126] Silicone elastomer microparticles are crosslinked products of linear diorganopolysiloxanes mainly composed of diorganosiloxy units (D units). Silicone elastomer microparticles can be prepared by crosslinking diorganopolysiloxanes by hydrosilylation reaction or condensation reaction of silanol groups, and can be preferably obtained by crosslinking an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the side chain or end with a diorganopolysiloxane having unsaturated hydrocarbon groups such as alkenyl groups at the side chain or end under a hydrosilylation reaction catalyst. Silicone elastomer microparticles can take various shapes such as spherical, flat, and irregular, but from the viewpoint of dispersibility, spherical is preferable, and among them, true sphere is more preferable. Examples of commercially available silicone elastomer microparticles include "Trefil E Series" and "EP Powder Series" manufactured by Toray Dow Corning Co., Ltd., and "KMP Series" manufactured by Shin-Etsu Chemical Co., Ltd. The silicone elastomer fine particles may be surface-treated. Examples of the surface treatment agent include methylhydrogenpolysiloxane, silicone resin, metal soap, silane coupling agent, inorganic oxides such as silica and titanium oxide, fluorine compounds such as perfluoroalkylsilane and perfluoroalkyl phosphate ester salt, and the like.
[0127] In addition, when the composition is used as a wavelength conversion material for LEDs, a phosphor may be blended as component (B) to convert the wavelength of light emitted from an optical semiconductor element. The phosphor is not particularly limited, and examples thereof include yellow, red, green, and blue light-emitting phosphors made of oxide-based phosphors, oxynitride-based phosphors, nitride-based phosphors, sulfide-based phosphors, oxysulfide-based phosphors, and the like, which are widely used in light-emitting diodes (LEDs). Examples of oxide-based phosphors include yttrium, aluminum, and garnet-based YAG-based green to yellow light-emitting phosphors containing cerium ions; terbium, aluminum, and garnet-based TAG-based yellow light-emitting phosphors containing cerium ions; and silicate-based green to yellow light-emitting phosphors containing cerium and europium ions. Examples of oxynitride-based phosphors include silicon, aluminum, oxygen, and nitrogen-based sialon-based red to green light-emitting phosphors containing europium ions. Examples of nitride phosphors include calcium, strontium, aluminum, silicon, and nitrogen-based Cusn-based red-emitting phosphors that contain europium ions. Examples of sulfide phosphors include ZnS-based green-emitting phosphors that contain copper ions and aluminum ions. Examples of oxysulfide phosphors include Y2O2S-based red-emitting phosphors that contain europium ions. In the present composition, two or more of these phosphors may be used in combination.
[0128] Furthermore, the composition may contain a thermally conductive filler or a conductive filler to impart thermal or electrical conductivity to the cured product. Examples of the thermally conductive filler or the conductive filler include fine metal powders such as gold, silver, nickel, copper, and aluminum; fine powders of ceramic, glass, quartz, organic resin, and the like, on whose surfaces metals such as gold, silver, nickel, and copper are vapor-deposited or plated; metal compounds such as aluminum oxide, magnesium oxide, aluminum nitride, boron nitride, and zinc oxide; graphite, and mixtures of two or more of these. When the composition is required to have electrical insulation, metal oxide powders or metal nitride powders are preferred, and aluminum oxide powder, zinc oxide powder, and aluminum nitride powder are particularly preferred.
[0129] The content of component (B) is not limited, but is preferably 10 to 50 volume % of the total composition, and particularly preferably in the range of 10 to 40 volume %. If the content of component (B) exceeds the upper limit, the resulting cured product tends to be hard, the tan δ value described below decreases, and the technical effects of the present invention, that is, the handling workability of the composition and the gap filling property during hot melting, decrease. In addition, the flexibility and mechanical strength of the resulting cured product at room temperature to high temperature become insufficient, and the stress relaxation property of the cured product may decrease.
[0130] [(C) component] Component (C) is a curing agent for curing component (A), and is not limited as long as it can cure component (A). When component (A) has an alkenyl group, component (C) is an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule and a hydrosilylation catalyst. When component (A) contains an alkenyl group and a hydrosilylation catalyst, component (C) may be only an organopolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule, but may also be used in combination with a hydrosilylation catalyst. When component (A) has an alkenyl group, component (C) may be an organic peroxide, or may also be used in combination with an organopolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule. On the other hand, when component (A) has silicon-bonded hydrogen atoms, component (C) is an organopolysiloxane having at least two alkenyl groups per molecule and a hydrosilylation catalyst; when component (A) has silicon-bonded hydrogen atoms and contains a hydrosilylation catalyst, component (C) may be solely an organopolysiloxane having at least two alkenyl groups per molecule, although a hydrosilylation catalyst may also be used in combination.
[0131] Examples of the organopolysiloxane in component (C) include the alkenyl group-containing organopolysiloxane represented by the aforementioned (a1) and / or (a2), and the silicon-bonded hydrogen atom-containing organopolysiloxane represented by the aforementioned (a3) and / or (a4).
[0132] When an organopolysiloxane is used as component (C), there are no limitations on its content, but in order for the composition to cure, it is preferable that the amount be within the range of 0.5 to 20 moles, or 1.0 to 10 moles, of silicon-bonded hydrogen atoms per mole of alkenyl groups in the composition.
[0133] Examples of the catalyst for hydrosilylation reaction include platinum catalysts, rhodium catalysts, and palladium catalysts, and platinum catalysts are preferred because they can significantly accelerate the curing of the composition. Examples of the platinum catalyst include platinum fine powder, chloroplatinic acid, alcohol solution of chloroplatinic acid, platinum-alkenylsiloxane complex, platinum-olefin complex, platinum-carbonyl complex, and catalysts in which these platinum catalysts are dispersed or encapsulated in thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, and platinum-alkenylsiloxane complexes are particularly preferred. Examples of the alkenylsiloxane include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxanes in which a part of the methyl groups of these alkenylsiloxanes is replaced with an ethyl group, a phenyl group, or the like, and alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes are replaced with an allyl group, a hexenyl group, or the like. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred because the stability of this platinum-alkenylsiloxane complex is good. In addition, from the viewpoint of improving the handling and workability and the pot life of the composition, a platinum-containing hydrosilylation reaction catalyst in the form of fine particles dispersed or encapsulated in a thermoplastic resin may be used. In addition, non-platinum metal catalysts such as iron, ruthenium, and iron / cobalt may be used as a catalyst for promoting the hydrosilylation reaction.
[0134] The amount of the hydrosilylation reaction catalyst added is preferably an amount such that the metal atoms are in the range of 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm, by mass, relative to the component (A).
[0135] Examples of organic peroxides include alkyl peroxides, diacyl peroxides, ester peroxides, and carbonate peroxides.
[0136] Examples of alkyl peroxides include dicumyl peroxide, di-tert-butyl peroxide, di-tert-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, tert-butylcumyl, 1,3-bis(tert-butylperoxyisopropyl)benzene, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.
[0137] Examples of diacyl peroxides include benzoyl peroxide, lauroyl peroxide, and decanoyl peroxide.
[0138] Examples of peroxy esters include 1,1,3,3-tetramethylbutyl peroxy neodecanoate, α-cumyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, tert-butyl peroxy neoheptanoate, tert-butyl peroxy pivalate, tert-hexyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, and tert-amyl peroxy-2-ethylhexanoate. , tert-butylperoxy-2-ethylhexanoate, tert-butylperoxyisobutyrate, di-tert-butylperoxyhexahydroterephthalate, tert-amylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxyacetate, tert-butylperoxybenzoate, and di-butylperoxytrimethyladipate are examples.
[0139] Examples of peroxycarbonates include di-3-methoxybutyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, diisopropyl peroxycarbonate, tert-butylperoxyisopropyl carbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, dicetyl peroxydicarbonate, and dimyristyl peroxydicarbonate.
[0140] The organic peroxide preferably has a half-life of 10 hours at a temperature of 90° C. or higher, or 95° C. or higher. Examples of such organic peroxides include dicumyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,3-bis(tert-butylperoxyisopropyl)benzene, di-(2-t-butylperoxyisopropyl)benzene, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.
[0141] The content of the organic peroxide is not limited, but is preferably within a range of 0.05 to 10 parts by mass, or 0.10 to 5.0 parts by mass, per 100 parts by mass of the component (A).
[0142] The composition may also contain other optional components, such as hot-melt fine particles other than component (A), a cure retarder, and an adhesion promoter, so long as the object of the present invention is not impaired.
[0143] As the hot-melt fine particles other than the component (A), one or more selected from various hot-melt synthetic resins, waxes, fatty acid metal salts, etc. can be used. The wax component exhibits low kinetic viscosity at high temperatures (150°C) and forms a melt with excellent fluidity. In addition, by using the wax component in combination with the components (A) to (C) of the present composition, the wax component in the melt of the present composition spreads rapidly throughout the entire composition at high temperatures, thereby lowering the viscosity of the substrate surface to which the molten composition is applied and the entire composition, and also rapidly lowering the surface friction of the substrate and the molten composition, thereby significantly increasing the fluidity of the entire composition. Therefore, the viscosity and fluidity of the molten composition can be significantly improved by adding only a small amount of the wax component to the total amount of the other components.
[0144] The wax component may be a petroleum wax such as paraffin as long as it satisfies the above-mentioned conditions of dropping point and kinetic viscosity when melted, but from the viewpoint of the technical effect of the present invention, it is preferable that the wax component is a hot melt component made of a fatty acid metal salt, and particularly preferable are metal salts of higher fatty acids such as stearic acid, palmitic acid, oleic acid, isononanoic acid, etc. Here, the type of the fatty acid metal salt is not particularly limited, and suitable examples include alkali metal salts such as lithium, sodium, potassium, etc.; alkaline earth metal salts such as magnesium, calcium, barium, etc.; and zinc salts.
[0145] Particularly preferred wax components are fatty acid metal salts with a free fatty acid content of 5.0% or less, more preferably 4.0% or less, and more preferably 0.05 to 3.5%. Examples of such components include at least one metal stearate. From the viewpoint of the technical effects of the present invention, it is preferred that this component essentially consists of one or more metal stearate salts, and it is most preferred to use a hot melt component with a melting point of 150°C or less selected from calcium stearate (melting point 150°C), zinc stearate (melting point 120°C), and magnesium stearate (melting point 130°C).
[0146] The amount of the wax component used is in the range of 0.01 to 5.0 parts by mass, and may be 0.01 to 3.5 parts by mass, or 0.01 to 3.0 parts by mass, based on 100 parts by mass of the entire composition. If the amount of the wax component used exceeds the upper limit, the adhesiveness and mechanical strength of the cured product obtained from the granular curable silicone composition of the present invention may be insufficient. If the amount used is less than the lower limit, sufficient fluidity may not be achieved when heated and melted.
[0147] Examples of the curing retarder include alkyne alcohols such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; enyne compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; alkenyl-containing low molecular weight siloxanes such as tetramethyltetravinylcyclotetrasiloxane and tetramethyltetrahexenylcyclotetrasiloxane; and alkynyloxysilanes such as methyl-tris(1,1-dimethylpropynyloxy)silane and vinyl-tris(1,1-dimethylpropynyloxy)silane. The content of this curing retarder is not limited, but is preferably within the range of 10 to 10,000 ppm by mass with respect to the present composition.
[0148] As the adhesion promoter, an organic silicon compound having at least one alkoxy group bonded to a silicon atom in one molecule is preferred. Examples of this alkoxy group include methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy groups, and particularly preferred is methoxy. Examples of groups bonded to silicon atoms other than the alkoxy group in the organic silicon compound include halogen-substituted or unsubstituted monovalent hydrocarbon groups such as alkyl groups, alkenyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl groups; epoxycyclohexylalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl groups; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl groups; acrylic group-containing monovalent organic groups such as 3-methacryloxypropyl groups; and hydrogen atoms. The organosilicon compound preferably has a group capable of reacting with the alkenyl group or silicon-bonded hydrogen atom in the composition, and more specifically, preferably has a silicon-bonded hydrogen atom or an alkenyl group.In addition, since it can provide good adhesion to various substrates, the organosilicon compound preferably has at least one epoxy-containing monovalent organic group in one molecule.Examples of such organosilicon compounds include organosilane compounds, organosiloxane oligomers, and alkyl silicates.Examples of the molecular structure of the organosiloxane oligomer or alkyl silicate include linear, partially branched linear, branched, cyclic, and net-like, and in particular, linear, branched, and net-like are preferred.Examples of the organosilicon compound include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds having at least one silicon-bonded alkenyl group or silicon-bonded hydrogen atom, and at least one silicon-bonded alkoxy group in one molecule; a mixture of a silane compound or siloxane compound having at least one silicon-bonded alkoxy group and a siloxane compound having at least one silicon-bonded hydroxy group and at least one silicon-bonded alkenyl group in one molecule; methyl polysilicate, ethyl polysilicate, and epoxy group-containing ethyl polysilicate. The adhesion promoter is preferably a low-viscosity liquid, and although there are no limitations on its viscosity, it is preferably within the range of 1 to 500 mPa·s at 25°C. Furthermore, the content of this adhesion promoter is not limited, but is preferably within the range of 0.01 to 10 parts by mass per 100 parts by mass of the total of the present composition.
[0149] Furthermore, the composition may contain other optional components, such as heat resistance agents such as iron oxide (red oxide), cerium oxide, cerium dimethylsilanolate, fatty acid cerium salts, cerium hydroxide, and zirconium compounds, as well as dyes, pigments other than white, and flame retardants, so long as the object of the present invention is not impaired.
[0150] The above composition, by using component (B) in combination with component (A), organopolysiloxane resin fine particles or a mixture containing the same, in a specific ratio, has excellent melting (hot melt) properties, and the cured product is flexible from room temperature to high temperatures, specifically from 25°C to 150°C, has excellent stress relaxation properties, and is not easily damaged even when deformation such as bending occurs at room temperature. The above component (B) preferably contains an inorganic filler, and further functionality such as improved light reflectance can be imparted by using a white pigment, a thermally conductive filler, an electrically conductive filler, a phosphor, or the like.
[0151] [Storage modulus of cured product] Specifically, the cured product obtained by curing the composition has a storage modulus (G') value of 2000 MPa or less at 25°C and a storage modulus (G') value of 100 MPa or less at 150°C. Such a cured product is flexible at both room temperature (25°C) and high temperature (150°C), has excellent adhesion and conformability to substrates such as semiconductor substrates, and even in applications for sealing semiconductor elements that are subject to deformation such as flexible semiconductor substrates that have been increasingly introduced in recent years, the occurrence of defects such as damage or peeling of the sealed semiconductor element and voids is suppressed. In applications requiring particularly high elongation and conformability to deformation, the storage modulus (G') value at 25°C may be 1500 MPa or less or 1000 MPa or less, and the storage modulus (G') value at 150°C may be 50 MPa or less or 40 MPa or less.
[0152] [Peak value and peak temperature of loss tangent (tan δ) of hardened material] Furthermore, the cured product obtained by curing the composition of the present invention must have a peak value of loss tangent (tan δ) defined as the ratio of storage modulus (G') to loss modulus (G'') at a frequency of 1.0 Hz, i.e., G' / G'', of 0.40 or more, preferably 0.50 or more, and particularly preferably in the range of 0.50 to 0.80. If the peak value of tan δ is less than 0.40, warping or breakage of the molded product may occur, particularly when the molded product is in the form of a thin film or is integrally molded with an aluminum lead frame or the like. The peak temperature giving the peak value of tan δ is not particularly limited, but is preferably in the range of 30 to 200°C, and particularly preferably in the range of 40 to 150°C.
[0153] In the composition of the present invention, a cured product having excellent stress relaxation ability is formed by making the peak value of tan δ 0.4 or more, and particularly, by suitably selecting the above components, a high peak value of tan δ can be realized even in a composition containing a relatively large amount of inorganic filler. Such a cured product realizes excellent low warpage ability in the large-area collective sealing process of semiconductors, which has been increasingly introduced in recent years. The peak value of tan δ can be controlled by the amount of the branched polyorganosiloxane component added in component (A), the amount of carbon-carbon double bonds in component (A), and the amount of component (B) added.
[0154] [Use of the composition] The composition may be used in the form of pellets. The pellets of the composition are obtained by tableting the composition, and are excellent in handling and hardening properties. The "pellets" are also called "tablets". The shape of the pellets is not limited, but they are usually spherical, elliptical or cylindrical. The size of the pellets is not limited, but they have an average particle diameter or circle equivalent diameter of, for example, 500 μm or more.
[0155] The present composition may be molded into a sheet for use. For example, a sheet made of a curable granular silicone composition having an average thickness of 100 to 1000 μm has hot melt properties and is heat curable at high temperatures, and is therefore advantageous in terms of excellent handling and melting properties, particularly when used for compression molding. Such a sheet-like composition may be produced by integrating the curable granular composition obtained by the above method at low temperature using a single- or double-screw continuous kneader, and then passing it through a two-roll mill or the like to a predetermined thickness.
[0156] [Use as a laminate and film adhesive] The present composition can be used in sheet form, and in particular can be used as a laminate having a structure including a sheet-like member made of the above-mentioned curable granular silicone composition between two film-like substrates equipped with a release layer.
[0157] There are no particular limitations on the method for producing such a peelable laminate, but a curable silicone sheet having hot melt properties can be produced using organopolysiloxane resin fine particles as a raw material, and the following method can be used: Step 1: Mixing organopolysiloxane resin particles, a curing agent, and a functional filler Step 2: A step of kneading the mixture obtained in step 1 while heating and melting it at a temperature of 120°C or less. Step 3: Laminating the heated, melted and kneaded mixture obtained in step 2 between two films, each having at least one release surface, to form a laminate; Step 4: A step of stretching the mixture in the laminate obtained in step 3 between rolls to form a curable hot melt silicone sheet having a specific thickness. The manufacturing method includes the steps of:
[0158] In the above manufacturing method, steps 3 and 4 may be continuous and integrated steps, for example, the mixture obtained after heating and melting in step 2 may be laminated by being discharged or applied between films having at least one release surface directly below the rolls, and at the same time, the gap between the rolls may be adjusted to stretch the film to a specific thickness. In this way, a manufacturing method having steps 3 and 4 substantially integrated is also included in the scope of the above manufacturing method. That is, steps 3 and 4 may be performed continuously and integrally by discharging or applying the mixture obtained in step 2 between two release films to sandwich the mixture between the two release films, for example, between two long release films, and passing the resulting laminate consisting of the two release films and the mixture sandwiched between them between rolls to stretch and mold the mixture between the release films and adjust the thickness to a predetermined value to obtain the desired laminate. Such a method of performing steps 3 and 4 integrally is also included in the above-mentioned production method.
[0159] In the above step 3, the step of laminating the mixture after heat melting between films is not particularly limited, and may be (i) a step of discharging or applying the mixture after heat melting from step 2 onto a first release film having a release surface, and then contacting the second release film with the surface of the mixture opposite to the surface contacting the first release film to interpose the mixture after heat melting between the first release film and the second release film, i.e., sandwiching the mixture; or (ii) a step of discharging or applying the mixture after heat melting from step 2 between the first release film and the second release film having a release surface to interpose the mixture after heat melting between both release films. (ii) can be exemplified by a method in which the first and second release films are brought close to each other by an appropriate means, such as two rolls, and the mixture from step 2 is discharged or applied at the location where the two release films are close to each other, and the mixture is sandwiched between the two release films simultaneously or almost simultaneously. It is particularly preferable that the above steps 3 and 4 are continuous steps.
[0160] The type of the film-like substrate is not particularly limited, and it is possible to appropriately use a polyester film, a polyolefin film, a polycarbonate film, an acrylic film, etc. It is preferable that the sheet-like substrate is non-porous.
[0161] The release layer is a necessary component for easily peeling off the sheet-like member made of the curable granular silicone composition from the film-like substrate, and may also be called a release liner, separator, release layer, or release coating layer.Preferably, the release layer may be a release layer having release coating ability such as a silicone-based release agent, a fluorine-based release agent, an alkyd-based release agent, or a fluorosilicone-based release agent, or a substrate itself that forms physically fine irregularities on the substrate surface, or is difficult to adhere to the adhesive layer made of the curable reactive silicone pressure-sensitive adhesive composition of the present invention or its cured product.In particular, in the laminate of the present invention, it is preferable to use a release layer made by curing a fluorosilicone-based release agent as the release layer.
[0162] The above laminate can be used, for example, by applying a sheet-like member made of the curable granular silicone composition to an adherend and then peeling the uncured sheet-like member from the film-like substrate.
[0163] Here, the sheet-like member made of the curable granular silicone composition may be a film-like adhesive having a thickness of 1 mm or less. That is, the laminate may include a peelable film-like adhesive held by a base film, and is preferred. The film-like adhesive has hot melt properties, and may be an adhesive used for temporary fixing of semiconductor members, or may be used as a die attachment film.
[0164] Furthermore, a sheet-like member made of the curable granular silicone composition may be molded as is onto a substrate by compression molding, press molding or the like, and in this case, molding may be carried out while leaving the film-like substrate on one side in place, which may be used as a release film to prevent adhesion to the mold during molding.
[0165] The present composition is non-fluid at 25°C. Here, non-fluid means that it does not deform or flow in an unloaded state, and preferably does not deform or flow in an unloaded state at 25°C when molded into pellets, tablets, or the like. Such non-fluidity can be evaluated, for example, by placing the molded composition on a hot plate at 25°C and finding that it does not substantially deform or flow even when unloaded or with a certain load is applied. If the composition is non-fluid at 25°C, the shape retention at that temperature is good and the surface tackiness is low.
[0166] The softening point of the present composition is preferably 100° C. or lower. Such a softening point means the temperature at which, when a load of 100 grams is applied to a hot plate for 10 seconds and the deformation of the composition is measured after the load is removed, the deformation in the height direction is 1 mm or more.
[0167] The viscosity of the composition tends to decrease rapidly under high temperature and high pressure (i.e., during the molding process), and it is preferable to use a value measured under similar high temperature and high pressure as a useful melt viscosity value. Therefore, it is preferable to measure the melt viscosity of the composition under high pressure using a Koka-shiki flow tester (manufactured by Shimadzu Corporation) rather than measuring it with a rotational viscometer such as a rheometer. Specifically, it is preferable that the melt viscosity of the composition at 150°C is 200 Pa·s or less, more preferably 150 or less. This is because the composition has good adhesion to the substrate after being cooled to 25°C after being hot melted.
[0168] This composition has excellent curing properties. The curing properties of this composition can be evaluated using a rheometer. The curing properties of this composition are expressed as T1 and T2, respectively, which are the times (seconds) at which a 1% torque value and a 90% torque value are obtained when the torque value after 3 minutes at a constant temperature of 150 to 180°C is taken as 100. 90 The composition can be evaluated based on the value of T1 when measured at a constant temperature of 150 to 180°C. The composition preferably has a T1 of 20 seconds or more, or 25 seconds or more when measured at a constant temperature of 150 to 180°C. 90 It is preferable that the time is 145 seconds or less, or 140 seconds or less. As a rheometer used for the measurement, for example, a rheometer MDR2000 (manufactured by Alpha Technologies Co., Ltd.) is mentioned.
[0169] [Method of producing a curable granular silicone composition] This composition can be produced by powder mixing components (A) to (C) and any other optional components at a temperature below the softening point of component (A). There are no limitations on the powder mixer used in this production method, and examples include a single- or double-screw continuous mixer, a twin roll, a Ross mixer, a Hobart mixer, a dental mixer, a planetary mixer, a kneader mixer, a laboratory miller, a small grinder, and a Henschel mixer, and preferably a laboratory miller, a small grinder, or a Henschel mixer.
[0170] [Molding method for the cured product] The present composition can be cured by a method comprising at least the following steps (I) to (III). (I) heating the composition to 50° C. or higher to melt it; (II) a step of injecting the curable silicone composition obtained in step (I) into a mold, or a step of spreading the curable silicone composition obtained in step (I) around the mold by clamping the mold; and (III) A step of curing the curable silicone composition injected in the step (II)
[0171] As described above, the present composition has excellent gap-filling properties when melted and excellent flexibility of the cured product at room temperature to high temperatures, and therefore can be very suitably used in a molding method including a covering step (so-called mold underfill method) in which the cured product is used to overmold and underfill a semiconductor element at the same time. Furthermore, due to the above-mentioned properties, the present composition can be suitably used in a molding method including a covering step (so-called wafer molding) in which the surface of a semiconductor wafer substrate carrying a single or multiple semiconductor elements is covered and overmolded so that the gaps between the semiconductor elements are filled with the cured product.
[0172] In the above steps, a transfer molding machine, a compression molding machine, an injection molding machine, an auxiliary ram type molding machine, a slide type molding machine, a double ram type molding machine, or a molding machine for low pressure encapsulation can be used. In particular, the composition of the present invention can be suitably used for the purpose of obtaining a cured product by transfer molding and compression molding. In particular, the composition of the present invention molded into a sheet shape is useful as a material for compression molding.
[0173] Finally, in step (III), the curable silicone composition injected (applied) in step (II) is cured. When an organic peroxide is used as component (C), the heating temperature is preferably 150° C. or higher, or 170° C. or higher.
[0174] Since the composition is suitable as a protective material for semiconductors, etc., it is preferable that the type D durometer hardness at 25° C. of the cured product obtained by curing the composition is not less than 20. The type D durometer hardness is determined using a type D durometer in accordance with JIS K 6253-1997 "Testing method for hardness of vulcanized rubber and thermoplastic rubber."
[0175] Furthermore, since the composition is suitable as an encapsulating material for semiconductors in flexible applications where flexibility is required, it is preferable that the bending elongation of the cured product measured by the method specified in JIS K 6911-1995 "General testing methods for thermosetting plastics" is 2% or more, or 4% or more.
[0176] [Use of the composition] The composition has hot melt properties and is excellent in gap filling properties, handling workability and curing properties when melted (hot melt), so it is suitable for use as a sealant or underfill agent for semiconductors; a sealant or underfill agent for power semiconductors such as SiC and GaN; a sealant or light reflector for optical semiconductors such as light-emitting diodes, photodiodes, phototransistors and laser diodes; and an adhesive, potting agent, protective agent and coating agent for electrical and electronic devices. In addition, the composition has hot melt properties, so it is also suitable as a material for transfer molding, compression molding or injection molding. In particular, it is suitable for use as a sealant for semiconductors that use a mold underfill method or a wafer molding method during molding. Furthermore, the composition in the form of a sheet can be used as a curable film adhesive or a stress buffer layer between two types of substrates with different linear expansion coefficients.
[0177] [Uses of the cured product] Although there are no particular limitations on the applications of the cured product of the present invention, the composition of the present invention has hot melt properties, excellent moldability and gap fill properties, and the cured product has the above-mentioned flexibility at room temperature, high stress relaxation properties, flexural elongation, etc. Therefore, the cured product obtained by curing the present composition can be suitably used as a semiconductor device member, and can be suitably used as an encapsulant for semiconductor elements, IC chips, etc., a light reflector for optical semiconductor devices, and an adhesive / bonding member for semiconductor devices.
[0178] Although there are no particular limitations on the type of semiconductor device that includes a member made of the cured product of the present invention, it is particularly preferred that the semiconductor device is a power semiconductor device, an optical semiconductor device, or a semiconductor device mounted on a flexible circuit board.
[0179] The curable granular silicone composition of the present invention, particularly a pellet- or sheet-shaped curable granular silicone composition, can be used for sealing a large area of a semiconductor substrate (including a wafer). Furthermore, a sheet obtained by molding the curable granular silicone composition of the present invention into a sheet shape can be used for die attach films, sealing of flexible devices, stress relief layers for bonding two different substrates, etc. EXAMPLES
[0180] The hot-melt curable silicone composition of the present invention and its manufacturing method will be described in detail with reference to examples and comparative examples. In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. The softening point of the curable silicone composition of each example and comparative example was measured by the following method. The curable silicone composition was heated at 150°C for 2 hours to prepare a cured product, and the storage modulus, loss tangent (tan δ), and warpage of the molded product were measured by the following methods. The results are shown in Table 1.
[0181] [Softening point of curable granular silicone composition] The curable granular silicone composition was molded into a cylindrical pellet of φ14 mm×22 mm. The pellet was placed on a hot plate set at 25° C. to 100° C., and pressed from above with a load of 100 grams for 10 seconds. After removing the load, the deformation of the pellet was measured. The temperature at which the deformation in the height direction became 1 mm or more was taken as the softening point.
[0182] [Storage modulus and tan δ of the cured product] The curable silicone composition was heated at 150°C for 2 hours to produce a cured product. The storage modulus and loss modulus of this cured product were measured from -50°C to 250°C using an ARES rheometer (manufactured by TA Instruments Japan, Inc.), and the storage modulus values at 25°C and 150°C, as well as the peak temperature and peak value of tan δ (storage modulus / loss modulus) were read. The results are shown in Table 1.
[0183] [Warping of molded products] The curable silicone composition was heated at 150°C for 2 hours on an aluminum plate measuring 60mm x 60mm x 0.4mm to form an integral molded product. In order to make the warping behavior easier to understand, a substrate that is prone to warping (a thin aluminum plate) was used for the evaluation. One side of the molded product obtained was fixed to a horizontal desk with tape, and the lift distance of the other side from the desk was measured using a ruler, which was taken as the warping value of the molded product.
[0184] Organopolysiloxane resins or crosslinked organopolysiloxanes containing a hydrosilylation catalyst were prepared by the methods shown in Reference Examples 1 to 6 below, and the presence or absence of hot melt properties was evaluated based on the presence or absence of softening point / melt viscosity. Also, organopolysiloxane resin fine particles were prepared by the methods shown in Reference Examples 3 to 6. In the Reference Examples, 1,1,3,3-tetramethyl-1,3-divinyldisiloxane used in the platinum complex, which is a hydrosilylation catalyst, is referred to as "1,3-divinyltetramethyldisiloxane."
[0185] [Reference example 1] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (PhSiO 3 / 2 ) 0.80 (Me2ViSiO 1 / 2 ) 0.20 270.5 g of a 55% by mass toluene solution of a resinous organopolysiloxane represented by the formula: HMe2SiO(Ph2SiO)SiMe2H 21.3 g (an amount such that there are 0.5 moles of silicon-bonded hydrogen atoms in this component per mole of vinyl groups in the resinous organopolysiloxane) of diphenylsiloxane capped with dimethylhydrogensiloxy groups at both molecular chain ends and having a viscosity of 5 mPa s (silicon-bonded hydrogen atom content = 0.6% by mass), and 0.43 g (an amount such that platinum metal would be 10 ppm by mass in the liquid mixture) of a 1,3-divinyltetramethyldisiloxane solution of platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = approximately 4000 ppm) were added and stirred uniformly at room temperature. The temperature in the flask was then raised to 100°C in an oil bath, and the mixture was stirred under toluene reflux for 2 hours to prepare a toluene solution of organosiloxane crosslinked product (1) that was made up of a resinous organosiloxane derived from the resinous organopolysiloxane and a linear organosiloxane derived from the diphenylsiloxane, and had a vinyl group that was not involved in the reaction. When this organosiloxane crosslinked product (1) was analyzed by FT-IR, no peaks of silicon-bonded hydrogen atoms were observed. The softening point of this organosiloxane crosslinked product (1) was 75°C, and its melt viscosity at 100°C was 700 Pa·s.
[0186] [Reference example 2] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (Me2ViSiO 1 / 2 ) 0.05 (Me3SiO 1 / 2 ) 0.39 (SiO 4 / 2 ) 0.56 (HO 1 / 2 ) 0.02 270.5 g of a 55 mass % xylene solution of an organopolysiloxane resin represented by the formula (1) and 0.375 g of a 1,3-divinyltetramethyldisiloxane solution of a platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = approximately 4000 ppm) were added and stirred uniformly at room temperature (25°C) to prepare a xylene solution of organopolysiloxane resin (2) containing 10 ppm by mass as platinum metal. Furthermore, this organopolysiloxane resin (2) did not soften / melt even when heated to 200°C, and did not have hot melt properties.
[0187] [Reference example 3] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (Me3SiO 1 / 2 ) 0.44 (SiO 4 / 2 ) 0.56 (HO 1 / 2 ) 0.02 270.5 g of a 55 mass % xylene solution of an organopolysiloxane resin represented by the formula (1) and 0.375 g of a 1,3-divinyltetramethyldisiloxane solution of a platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = about 4000 ppm) were added and stirred uniformly at room temperature (25°C) to prepare a xylene solution of organopolysiloxane resin (3) containing 10 ppm by mass as platinum metal. Furthermore, this organopolysiloxane resin (3) did not soften / melt even when heated to 200°C, and did not have hot melt properties.
[0188] [Reference Example 4: Hot-melt organopolysiloxane resin microparticles (1)] The toluene solution of the organosiloxane crosslinked product (1) prepared in Reference Example 1 was atomized by spray drying at 40° C. while removing the toluene, to prepare spherical hot-melt silicone microparticles (1). When the microparticles were observed with an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 7.5 μm.
[0189] [Reference Example 5: Non-hot melt organopolysiloxane resin fine particles (2)] The xylene solution of organopolysiloxane resin (2) prepared in Reference Example 1 was granulated at 50° C. by a spray method using a spray dryer while removing the xylene, to prepare spherical non-hot melt organopolysiloxane resin microparticles (2). When the microparticles were observed under an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 6.9 μm.
[0190] [Reference Example 6: Non-hot melt organopolysiloxane resin fine particles (3)] The xylene solution of organopolysiloxane resin (3) prepared in Reference Example 2 was granulated at 50° C. by a spray method using a spray dryer while removing the xylene, to prepare spherical non-hot melt organopolysiloxane resin microparticles (3). When the microparticles were observed under an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 7.4 μm.
[0191] [Example 1] Hot melt silicone microparticles (1) 73.1g, Formula: HMe2SiO(Ph2SiO)SiMe2H 9.5 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), The viscosity is 1,000 mPa s. Average formula Me2ViSiO(MePhSiO) 17.5 SiMe2Vi Methylphenylpolysiloxane terminated at both ends of the molecular chain with dimethylvinylsiloxy groups (vinyl group content = 2.1% by mass) {an amount such that the diphenylsiloxane contains 0.9 moles of silicon-bonded hydrogen atoms per 1.0 mole of vinyl groups in the silicone fine particles (1) and the methylphenylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups}, 1-ethynyl-1-cyclohexanol (in an amount equivalent to 300 ppm by mass of the composition), 24.0 g of fused silica (SP60 manufactured by Nippon Steel Materials Micron Co., Ltd.) with an average particle size of 2.5 μm, and 30.0 g of fumed silica (AEROSIL50 from Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0192] [Example 2] Hot melt silicone microparticles (1) 89.3g, Formula: HMe2SiO(Ph2SiO)SiMe2H 10.7 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), {the amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles per 1.0 mole of vinyl groups in the silicone microparticles (1)}, 1-ethynyl-1-cyclohexanol (in an amount equivalent to 300 ppm by mass of the composition), 98.0 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm; 4.0 g of fumed silica (AEROSIL50 from Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0193] [Example 3] (a+c(pt)) 58.5 g of non-hot melt organopolysiloxane resin fine particles (3) (vinyl group content = 0 mass%), (a+c(pt)) 10.3 g of non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 1.91% by mass), Formula (b1): ViMe2SiO(Me2SiO) 800SiViMe2 29.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.09% by mass), (c4(SiH)) formula: Me3SiO(MeHSiO)7(Me2SiO) 6.5 SiMe3 1.57 g of an organohydrogenpolysiloxane represented by the formula {an amount such that the organohydrogenpolysiloxane contains 1.3 moles of silicon-bonded hydrogen atoms per mole of vinyl groups in the organopolysiloxane resin fine particle (2) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d1) 203.1 g of alumina having an average particle size of 0.44 μm (AES-12 manufactured by Sumitomo Chemical Co., Ltd.); 1-ethynyl-1-cyclohexanol (in an amount equivalent to 1000 ppm by mass of the composition) was added all at once to a small grinder and stirred at room temperature (25°C) for 1 minute to prepare a uniform curable granular silicone composition. Additionally, the results of measuring the softening point and other properties of this composition are shown in Table 1.
[0194] [Example 4] (a+c(pt)) Non-hot melt organopolysiloxane resin fine particles (3) (vinyl group content = 0 mass%) 55.3 g, (a+c(pt)) 13.8 g of non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 1.91% by mass), Formula (b1): ViMe2SiO(Me2SiO) 800 SiViMe2 29.6 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.09% by mass), (c2(SiH)) formula: (HMeSiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 1.1 g of organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) {an amount such that the organohydrogenpolysiloxane resin contains 1.1 moles of silicon-bonded hydrogen atoms per mole of vinyl groups in the organopolysiloxane resin fine particles (2) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d1) 232.6 g of alumina having an average particle size of 0.44 μm (AES-12 manufactured by Sumitomo Chemical Co., Ltd.); 1-ethynyl-1-cyclohexanol (in an amount equivalent to 1000 ppm by mass of the composition) was added all at once to a small grinder and stirred at room temperature (25°C) for 1 minute to prepare a uniform curable granular silicone composition. Additionally, the results of measuring the softening point and other properties of this composition are shown in Table 1.
[0195] [Comparative Example 1] Hot melt silicone microparticles (1) 89.3 g, formula: HMe2SiO(Ph2SiO)SiMe2H 10.7 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), {The amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles relative to 1.0 mole of vinyl group in silicone fine particles (1)}, 1-ethynyl-1-cyclohexanol (the amount of 300 ppm by mass relative to this composition), 298.5 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm, and 1.5 g of fumed silica (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm are put into a small grinder at once, and stirred at room temperature (25 ° C) for 1 minute to prepare a uniform curable granular silicone composition.In addition, the measurement results such as the softening point of this composition are shown in Table 1.
[0196] [Comparative Example 2] Hot melt silicone microparticles (1) 89.3g, Formula: HMe2SiO(Ph2SiO)SiMe2H 10.7 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), {the amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles per 1.0 mole of vinyl groups in the silicone microparticles (1)}, 1-ethynyl-1-cyclohexanol (in an amount equivalent to 300 ppm by mass of the composition), 235.0 g of fused silica with an average particle size of 2.5 μm (SP60 manufactured by Nippon Steel Materials Micron Co., Ltd.) The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0197] [Comparative Example 3] Hot melt silicone microparticles (1) 89.3g, Formula: HMe2SiO(Ph2SiO)SiMe2H 7.4 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), Average unit formula: (PhSiO 3 / 2 ) 0.4 (HMeSiO 1 / 2 ) 0.6 3.1 g of a branched-chain organopolysiloxane having two or more silicon-bonded hydrogen atoms in one molecule and a viscosity of 25 mPa s (content of silicon-bonded hydrogen atoms = 0.65% by mass). {the amount of silicon-bonded hydrogen atoms in the diphenylsiloxane and the branched organopolysiloxane is 0.9 moles per 1.0 mole of vinyl groups in the silicone microparticles (1)}, 1-ethynyl-1-cyclohexanol (in an amount equivalent to 300 ppm by mass of the composition), 232.0 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm; 1.5g of fumed silica (AEROSIL50 from Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0198] [Comparative Example 4] Hot melt silicone microparticles (1) 45.0 g, The viscosity is 20,000 mPa s. Average formula Me2ViSiO(MePhSiO) 92 SiMe2Vi Methylphenylpolysiloxane terminated at both ends of the molecular chain with dimethylvinylsiloxy groups (vinyl group content = 0.63% by mass) Formula: HMe2SiO(Ph2SiO)SiMe2H 1.0 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), Average unit formula: (PhSiO 3 / 2 ) 0.4 (HMeSiO 1 / 2 ) 0.6 6.3 g of a branched-chain organopolysiloxane having two or more silicon-bonded hydrogen atoms in one molecule and a viscosity of 25 mPa s (content of silicon-bonded hydrogen atoms = 0.65% by mass). {the amount of silicon-bonded hydrogen atoms in the diphenylsiloxane and the branched organopolysiloxane is 0.9 moles per 1.0 mole of vinyl groups in the silicone microparticles (1)}, 1-ethynyl-1-cyclohexanol (in an amount equivalent to 300 ppm by mass of the composition), 98.0 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm; 4.0 g of fumed silica (AEROSIL50 from Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0199] [Comparative Example 5] (a+c(pt)) 34.1 g of non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 0 mass%), (a+c(pt)) Hot melt properties 34.1 g of organopolysiloxane resin fine particles (1) (vinyl group content = 1.91% by mass), (b2) Formula: ViMe2SiO(Me2SiO) 140 SiViMe2 14.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.44% by mass), (b3) Formula: ViMe2SiO(Me2SiO) 300 SiViMe2 14.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.21% by mass), (c2(SiH)) formula: (HMe2SiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 Organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) represented by the formula: {an amount such that the organohydrogenpolysiloxane resin contains 1.1 moles of silicon-bonded hydrogen atoms per mole of vinyl groups in the organopolysiloxane resin fine particles (1) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d2) 142.6 g of titanium oxide having an average particle size of 0.5 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.); (d3) 10.3 g of fumed silica having an average particle size of 0.04 μm (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.); 1-ethynyl-1-cyclohexanol (amount equivalent to 1000 ppm by mass of the composition) The above was added all at once to a small grinder and stirred for 1 minute at room temperature (25°C) to prepare a uniform curable granular silicone composition. The results of measurements of the softening point and other properties of this composition are shown in Table 1.
[0200] [Comparative Example 6] (a+c(pt)) Non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 0 mass%) 41.3 g, (a+c(pt)) Hot melt properties 27.5 g of organopolysiloxane resin fine particles (1) (vinyl group content = 1.91% by mass), (b4) Formula: ViMe2SiO(Me2SiO) 45 SiViMe2 27.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 1.53% by mass), (c2(SiH)) formula: (HMe2SiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 Organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) {an amount such that the amount of silicon-bonded hydrogen atoms in the organohydrogenpolysiloxane resin is 1.0 mole per mole of vinyl groups in the organopolysiloxane resin fine particles (1) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d2) 299.0 g of titanium oxide having an average particle size of 0.5 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.); (d3) 1.5 g of fumed silica having an average particle size of 0.04 μm (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.); 1-ethynyl-1-cyclohexanol (in an amount equivalent to 1000 ppm by mass relative to the composition) was added to a small grinder all at once and stirred at room temperature (25°C) for 1 minute to prepare a uniform white curable granular silicone composition. The results of measurements of the softening point of this composition are also shown in Table 1.
[0201] TIFF0007644604000001.tif101117
[0202] [Summary] The curable granular silicone compositions of Examples 1 to 4 according to the present invention have good hot melt properties. Furthermore, the storage modulus of the cured products at 25°C and 150°C meets the requirements of the present invention, and the peak value of tan δ, expressed as storage modulus / loss modulus (G' / G''), is sufficiently high, so that even in integral molding using aluminum plates that are prone to warping, no warping or damage occurred in the molded products. For this reason, it is expected that the cured products obtained using these curable granular silicone compositions will have excellent stress relaxation properties and will be suitable for thin-layer encapsulation of semiconductors and large-area batch encapsulation processes for semiconductors.
[0203] On the other hand, in Comparative Examples 1 to 6 which do not satisfy the compositional requirements of the present invention or the requirements relating to the storage modulus and peak value of tan δ at 25°C and 150°C, the molded product warped by 1 mm or more during integral molding using an aluminum plate, and the cured product did not achieve sufficient stress relaxation properties.
[0204] <Production Example 1> The granulated curable silicone composition of Example 1 and the like is heated to 80°C, and is melt-kneaded by using a twin-screw extruder, and is fed in the form of a semi-solid softened material onto a peelable film (FL2-01, manufactured by Takara Corporation) at a feed rate of 5 kg / hour, and is laminated between two peelable films. The laminate is then stretched between rolls to form a laminate in which a hot-melt curable silicone sheet having a thickness of 500 μm is laminated between two peelable films, and the whole is cooled by a cooling roll set at −15°C. The peelable film is separated from the laminate to obtain a flat and homogeneous hot-melt curable silicone sheet.
[0205] <Production Example 2> The granulated curable silicone composition of Example 1 and the like is heated to 80°C, melted and kneaded using a twin-screw extruder, and molded into a roughly sheet-like shape using a T-shaped die (opening size: 800 μm×100 mm, heated to 80°C). The composition is fed onto a release film (FL2-01, manufactured by Takara Corporation) at a feed rate of 5 kg / hour, and the whole is cooled using a cooling roll set to −15°C, and then laminated between two release films. The laminate is then stretched between rolls to form a laminate in which a 500 μm thick hot-melt curable silicone sheet is laminated between two release films. In the laminate, the release film is separated to obtain a flat and homogeneous hot-melt curable silicone sheet.
Claims
1. (A) organopolysiloxane resin fine particles, (B) one or more inorganic fillers selected from a reinforcing filler, a white pigment, a thermally conductive filler, a conductive filler, or a phosphor; and (C) Hardener The composition comprises The component (A) is (A2-1) Organopolysiloxane resin fine particles having a softening point of 200° C. or higher as a whole molecule, and (A2-2) A linear or branched organopolysiloxane that is liquid at 25°C and has a curing reactive functional group containing at least two carbon-carbon double bonds in the molecule. is a mixture of The component (A2-1) comprises (A2-1-2) organopolysiloxane resin fine particles which have a curing reactive functional group containing at least one carbon-carbon double bond in the molecule and contain siloxane units represented by SiO 4 / 2 in an amount of at least 20 mol % of all siloxane units; By hardening, The storage modulus (G') at 25°C is 2000 MPa or less, The storage modulus (G') at 150°C is 100 MPa or less, A curable granular silicone composition which gives a cured product having a peak loss tangent (tan δ) of 0.40 or greater, expressed as storage modulus / loss modulus (G' / G'') at a frequency of 1.0 Hz.
2. The component (A2-2) is (A2-2-1) The following structural formula: R 4 3 SiO(SiR 4 2 O) k SiR 4 3 (In the formula, each R 4 are independently monovalent hydrocarbon groups having 1 to 10 carbon atoms, provided that R 4 at least two of the groups are alkenyl groups, and k is a number from 20 to 5,000.
2. The curable granular silicone composition according to claim 1, which is a linear diorganopolysiloxane represented by the formula:
3. The component (A) is (A2-1-1) A compound that does not have hot melt properties as a whole molecule, does not have a curing reactive functional group containing a carbon-carbon double bond in the molecule, and has SiO 4/2 100 parts by mass of organopolysiloxane resin fine particles containing siloxane units represented by the formula: 3 to 50 parts by mass of component (A2-1-2), and (A2-2-1) Component 15 to 100 parts by mass 3. The curable granular silicone composition according to claim 2, which is a mixture comprising:
4. The curable granular silicone composition according to any one of claims 1 to 3, wherein the amount of component (B) is in the range from 10 to 50 volume % relative to the total volume of the composition.
5. A laminate having a structure comprising a sheet-like member made of the curable granular silicone composition according to any one of claims 1 to 4, between two film-like substrates each having a release layer.
6. 6. The laminate of claim 5, wherein the sheet-like member made of the curable granular silicone composition according to any one of claims 1 to 4 has a thickness of 1 mm or less and is a film-like adhesive.
7. A cured product obtained by curing the curable granular silicone composition according to any one of claims 1 to 4.
8. Use of the cured product according to claim 7 as a member for a semiconductor device.
9. A semiconductor device comprising the cured product according to claim 7.
10. A method for producing the curable granular silicone composition according to any one of claims 1 to 4, characterized in that the components constituting the curable granular silicone composition are granulated by mixing only the components at a temperature not exceeding 50°C.
11. A method for molding a cured product comprising at least the following steps (I) to (III): (I) a step of heating the cured product obtained by curing the curable granular silicone composition according to any one of claims 1 to 4 into pellets or a sheet at 100°C or higher to melt it; (II) a step of injecting the liquid curable silicone composition obtained in step (I) into a mold, or a step of spreading the curable silicone composition obtained in step (I) throughout the mold by clamping the mold; and (III) A step of curing the curable silicone composition injected in the step (II)
12. 12. A method for molding a cured product according to claim 11, comprising a coating step of carrying out overmolding and underfilling of a semiconductor element in one step with a cured product obtained by curing the curable granular silicone composition according to any one of claims 1 to 4.
13. 12. A method for molding a cured product according to claim 11, comprising a covering step of covering a surface of a semiconductor wafer substrate carrying one or more semiconductor elements with a cured product obtained by curing the curable granular silicone composition according to any one of claims 1 to 4, and overmolding the surface so that gaps between the semiconductor elements are filled with the cured product.
Citation Information
Patent Citations
Curable silicone composition, cured product thereof, and optical semiconductor device
JP2013076050A
Thermosetting silicone resin composition for reflector of LED, reflector for LED using the same and optical semiconductor apparatus
JP2013221075A
Reactive silicone composition, reactive thermoplastic body, cured product and optical semiconductor device
JP2014009322A
Curable resin composition, tablet of curable resin composition, molded body, semiconductor package, semiconductor component and light emitting diode
WO2013051600A1
Curable silicone composition, cured object obtained therefrom, and optical semiconductor device
WO2016038836A1